Phosphosilicon bifunctional comonomer, method of making, polymerizable monomer, precursor solution, lithium ion battery, and method of making
Patent Information
- Application Number
- CN202611180242.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-23
AI Technical Summary
一是传统的添加剂,如单体,功能相对单一,需要添加多种不同功能的单体来满足电池的各项性能要求;
一是功能多样化:本发明磷硅双功能共聚单体,是集“不饱和双键聚合位点、磷系阻燃官能团、笼型硅氧烷锚固结构”于一体的单分子三功能结构,单分子集成“聚合交联、界面锚固、本征阻燃、缺陷封堵”四大核心功能,解决了现有技术中单体结构功能单一的不足;
Smart Images

Figure CN122958489A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a phosphorus-silicon bifunctional comonomer and its preparation method, a polymerizable monomer, a precursor solution, a lithium-ion battery, and its preparation method. Background Technology
[0002] High-nickel ternary cathodes (NCM811, NCM955, NCM9 series) are the core cathode materials for improving the energy density of current power batteries due to their ultra-high specific capacity. Silicon-carbon anodes, compared to traditional graphite anodes, theoretically have a more than 10-fold increase in specific capacity, making them the only mainstream anode system for achieving high-energy-density batteries when matched with high-nickel cathodes. Lithium-ion battery electrolytes are complex multi-component systems, mainly composed of organic solvents, electrolyte lithium salts, and functional additives. Existing electrolytes and batteries have the following shortcomings: First, there are traditional additives, such as monomers, which have relatively simple functions. Multiple monomers with different functions need to be added to meet the various performance requirements of the battery. Secondly, traditional liquid electrolyte systems contain free liquid solvents, have low flash points, and are extremely flammable. When the battery is punctured or damaged by impact, the electrolyte will leak, and when exposed to high temperatures or short-circuit sparks, it will ignite and explode instantly. Moreover, the liquid electrolyte decomposes violently at high temperatures, forming a vicious cycle of "gas production - heat accumulation - internal short circuit - thermal runaway", with extremely low safety redundancy. Thirdly, high-nickel ternary cathodes have high nickel content and poor structural stability, with a lot of residual alkaline substances on the material surface. Under high temperature, overcharge, and fast charge conditions, they are prone to lattice collapse and release of active oxygen, which violently catalyzes the oxidation and decomposition of the electrolyte, generating a large amount of heat and gas, and easily triggering thermal runaway. At the same time, high-nickel cathodes have severe dissolution of transition metal ions, which shuttle to the surface of the anode, causing local interface degradation and micro-short circuit hazards. Fourthly, the silicon-carbon anode undergoes a massive volume expansion and contraction of 200%–300% during charging and discharging, causing the SEI film on the anode surface to repeatedly rupture, regenerate, and thicken. This continuously consumes electrolyte and generates gas, resulting in cell bulging and interface contact failure. At the same time, the volume deformation causes uneven current density distribution on the electrode surface, which can easily induce lithium dendrite growth under fast charging and low-temperature conditions, piercing the separator and causing internal short circuits, further inducing fire and explosion. Fifth, existing improvement solutions mostly focus on single electrode coating, a small amount of electrolyte flame retardant additives, and diaphragm modification, which can only slightly improve local performance and cannot fundamentally solve the systemic safety problems of flammable leakage of liquid electrolyte, failure of silicon-carbon expansion interface, and oxygen release and heat release of high-nickel cathode. Sixth, conventional gel curing technology has problems such as high curing temperature, high ionic impedance after curing, poor compatibility with the large expansion of silicon-carbon, weak flame retardant effect, and gel network cracking failure during cycling, making it difficult to simultaneously achieve high safety, high energy density and long cycle life. SUMMARY
[0003] The application aims to solve the problems in the prior art, and provides a phosphorus-silicon bifunctional comonomer, a preparation method thereof, a polymerizable monomer, a precursor solution, a lithium ion battery and a preparation method, which diversify the functions of monomers, prevent liquid leakage and combustion, inhibit thermal runaway, stabilize the positive and negative electrode interface, eliminate the growth conditions of lithium dendrites and greatly improve the overall safety of high-nickel silicon-carbon system batteries.
[0004] To achieve the above-mentioned purpose, the technical scheme adopted by the application is: A phosphorus-silicon bifunctional comonomer, characterized in that the chemical structural formula thereof is as follows: .
[0005] The phosphorus-silicon bifunctional comonomer has a molecular structure with a polymeric group of an acrylic double bond at one end, a phosphorus-oxygen flame-retardant molecular chain grafted at the middle end and a rigid anchoring structure of a cage-shaped siloxane at the terminal end, and is a new monomolecular three-function structure integrating an unsaturated double bond polymerization site, a phosphorus-based flame-retardant functional group and a cage-shaped siloxane anchoring structure.
[0006] A preparation method of a phosphorus-silicon bifunctional comonomer, characterized in that the method comprises the following steps: First step: raw material pretreatment: cage-shaped epoxy hemisiloxane (EP-POSS), allyl diethyl phosphate and hydroxyethyl acrylate are used as reaction raw materials, anhydrous tetrahydrofuran (THF) is used as a reaction solvent, triethylamine is used as an acid-binding agent and a catalyst, and the above raw materials are subjected to water removal treatment; Second step: low-temperature nucleophilic addition reaction: under the protection of nitrogen and in an anhydrous and oxygen-free environment, the cage-shaped epoxy hemisiloxane EP-POSS and the allyl diethyl phosphate are added to the anhydrous THF solvent, stirred and dissolved in an ice water bath at 0-5℃, triethylamine is slowly added dropwise, and after the dropwise addition is completed, constant-temperature reaction is carried out for 2h, so that the phosphorus-oxygen functional group is covalently grafted to the surface of the cage-shaped siloxane skeleton to obtain a phosphorus-functionalized POSS intermediate; Third step: end group double bond grafting modification: the reaction system is warmed to 25-30℃, hydroxyethyl acrylate is slowly added dropwise, and continuous stirring reaction is carried out for 4-6h, so that the ring-opening addition reaction of the hydroxyl group and the epoxy group is used to graft the active double bond polymerization site of the acrylic acid at the terminal end of the molecule to obtain the target crude product with the functions of double bond polymerization activity, phosphorus-based flame retardation and siloxane anchoring; Fourth step, purification and drying: after the reaction, the organic phase is collected by washing the reaction mixture with deionized water to remove the triethylamine salt byproduct; THF solvent is removed by rotary evaporation, and then water and impurities are removed by vacuum drying; finally, a light yellow transparent viscous liquid is obtained, which is named as allyl phosphonate cage siloxane acrylate, abbreviated as APSA monomer, which breaks the inherent defects of simple compounding and functional fragmentation of commercial monomers in the industry, integrates four core functions of "polymerization and crosslinking, interface anchoring, intrinsic flame retardation, and defect plugging" in a single molecule, accurately constructs an asymmetric functional molecular structure of "cage siloxane anchoring end-phosphorus oxygen flame retardant chain-acrylic polymerization double bond" through an original low-temperature addition grafting synthesis route; relying on the differential polymerization kinetics characteristics of the monomer, a gradient crosslinking network of "interface rigid anchoring, bulk flexible buffering, and overall molecular flame retardation" is formed in situ, which can not only effectively stabilize the interface of high-nickel positive electrode, inhibit metal dissolution and oxygen evolution side reactions, but also adapt to the 200%-300% ultra-large volume deformation of silicon-carbon negative electrode, and completely eliminate the problems of repeated rupture of SEI, lithium dendrite growth, and cell gas production, thus solving the inherent safety contradiction of high-nickel / silicon-carbon system from the molecular root.
[0007] The molar ratio of the cage-type epoxy hemisiloxane (EP-POSS), allyl diethyl phosphate, and hydroxyethyl acrylate is 1:(0.9-1.1):(1.05-1.3).
[0008] The content of the anhydrous tetrahydrofuran (THF) is 5-7 times the total mass of the cage-type epoxy hemisiloxane (EP-POSS), allyl diethyl phosphate, and hydroxyethyl acrylate.
[0009] The addition amount of the triethylamine is 3%-5% of the total molar amount of the reaction system.
[0010] In the fourth step, the temperature of vacuum drying is 45°C, and the drying time is 12h.
[0011] The molecular weight of the APSA monomer is 1180-1220 g / mol.
[0012] The cage-type epoxy hemisiloxane (EP-POSS) is T8 type octa-glycidyl ether propyl cage-type epoxy hemisiloxane (EP-POSS).
[0013] In the first step, the EP-POSS is vacuum dried at 60°C for 8h, the allyl diethyl phosphate and the hydroxyethyl acrylate are dried by molecular sieves, the anhydrous tetrahydrofuran is obtained by sodium wire reflux dehydration distillation, and the triethylamine is dried by calcium hydride.
[0014] A polymerizable monomer, characterized in that: the polymerizable monomer comprises APSA monomers prepared by the preparation method of the phosphorus-silicon bifunctional comonomer and polyethylene glycol diacrylate (PEGDA) monomers, the APSA monomers have high activity of acrylic double bonds, and polymerization is preferentially started at a low-temperature thermal initiation stage, and a dense polymerization layer is quickly formed at the interface of the positive and negative electrodes; the end cage siloxane structure of the monomers can be physically embedded and chemically anchored with the surface hydroxyl groups of the high-nickel positive electrode and the SEI defect sites of the silicon-carbon negative electrode, thereby realizing super strong interface bonding, precisely plugging oxygen release defects of the high-nickel positive electrode, inhibiting transition metal dissolution, and simultaneously restraining micro-deformation of the silicon-carbon negative electrode to prevent repeated rupture of the SEI; the phosphorus-oxygen groups covalently bonded in the middle of the molecule are fixed in the electrolyte network by the polymerization skeleton, thereby realizing intrinsic flame retardation of the single molecule, no precipitation and no failure, and the flexible PEGDA auxiliary monomer is used for co-crosslinking, the flexible long chain of the PEGDA is inserted into the gap between the rigid polymerization network of the APSA, a new crosslinking system of "rigid-flexible coupling and in-situ self-grading" is constructed, an integrated structure of high anchoring at the interface, high flexibility in the bulk and high flame retardation is spontaneously formed, and the structure is perfectly adapted to the 200%-300% super-large expansion of the silicon-carbon negative electrode, and simultaneously solves the problems of high-temperature corrosion and thermal runaway of the high-nickel positive electrode.
[0015] The mass ratio of the APSA monomers to the PEGDA monomers is 20-25:75-80.
[0016] The polymerizable monomer further comprises vinyl carbonate (VC), and a small amount of VC is used to assist in optimizing the interface film morphology and further reduce the interface impedance.
[0017] A precursor solution, characterized in that: the precursor solution is composed of a basic electrolyte, the polymerizable monomer, an initiator and inorganic flame-retardant fillers, wherein the proportions of the components are as follows: the basic electrolyte is 60%-70%, the polymerizable monomer is 20%-25%, the initiator is 0.5%-1.0%, and the inorganic flame-retardant fillers are 5%-10%.
[0018] The basic electrolyte is a composite three-salt system, which comprises LiPF6, LiBF4 and LiDFOB, and the solvent is a composite solvent of EC, DMC and FEC; LiDFOB can form a stable CEI film on the surface of the positive electrode to inhibit oxygen release and metal dissolution of the high-nickel positive electrode; FEC can optimize the SEI film structure of the silicon-carbon negative electrode to improve the flexibility and stability of the interface; and LiBF4 improves the high-temperature stability of the electrolyte and the flame-retardant substrate performance.
[0019] The proportions of LiPF6, LiBF4 and LiDFOB are 1.0:0.2:0.1, and the volume ratio of EC, DMC and FEC is 3:5:2.
[0020] The initiator described in the application is AIBN azobisisobutyronitrile, which can realize low-temperature thermal initiation of polymerization at 50-60 DEG C, and avoid damage to the structure of high-nickel positive electrode and silicon-carbon negative electrode caused by high-temperature treatment.
[0021] The inorganic flame-retardant filler described in the application is a compound of nano Al2O3 and EP-POSS cage-type silsesquioxane at a mass ratio of 3:1, wherein the nano Al2O3 improves the heat resistance, insulation and impact resistance of the system, the EP-POSS cage-like porous structure can strongly lock the electrolyte, prevent the leakage of free liquid, and at the same time improve the strength of the crosslinked network and the flame-retardant inhibition capability.
[0022] A lithium ion battery, comprising a positive electrode, a negative electrode and a separator, characterized in that it further comprises the precursor solution described above.
[0023] The positive electrode described in the application is NCM811 or NCM955 high-nickel ternary material, which is doped with Al³⁺ and Zr 4 ⁺ double-element lattices, the total mole fraction of doping is 0.5%-1.0%, and the surface is uniformly coated with a 5-10 nm LiPO3 inorganic ceramic protective layer, the double-element doping can stabilize the positive electrode layer lattice, inhibit high-temperature oxygen release and lattice collapse; the LiPO3 coating layer can block the contact between the electrolyte and the positive electrode active interface, greatly reduce the transition metal dissolution and the interface side reaction, and improve the positive electrode thermal stability and pressure resistance.
[0024] The negative electrode described in the application is a nano-silicon-carbon nanotube-graphite composite silicon-carbon material, and the silicon content is 15%-20%; the negative electrode surface is uniformly coated with a 1-2 mu m rigid conductive composite coating, the coating is composed of carbon nanotubes and polyimide resin, the three-dimensional carbon network structure can buffer the ultra-large volume expansion of silicon, the rigid coating can constrain the overall deformation of the negative electrode, avoid the repeated damage and regeneration of the SEI film, uniformly distribute the current on the electrode surface, and inhibit the growth of lithium dendrites and the negative electrode gas production from the root.
[0025] The separator described in the application is a polypropylene-based ceramic coated separator, the surface of which is coated with a 2-3 mu m aluminum oxide ceramic coating, the heat shrinkage temperature of the separator is greater than or equal to 180 DEG C, which can effectively resist high-temperature shrinkage and resist lithium dendrite puncture, and improve the internal short circuit protection capability of the battery cell.
[0026] A lithium ion battery preparation method, characterized in that it comprises the following steps: S1, preparing a precursor solution, stirring uniformly and then vacuum degassing; S2, assembling the positive and negative electrodes and the separator to form a battery cell; S3, injecting the precursor solution obtained in step S1 into the battery cell formed in step S2 under vacuum conditions; standing for infiltration at room temperature for 2h, initiating polymerization at 55 DEG C for 3-5h, and forming a gel electrolyte in situ; the whole solidification process is at a temperature of less than or equal to 60 DEG C, without high-temperature damage to the electrode structure, and without free liquid electrolyte in the battery cell; cooling, sealing, formation, and capacity distribution are performed to obtain a finished battery.
[0027] The battery has an energy density of greater than or equal to 380 Wh / kg, and does not catch fire, explode, or leak during the whole process of safety tests such as high-temperature heat box, needle puncture, heavy impact, and 8V overcharge.
[0028] Compared with the prior art, the present application has the following beneficial effects: First, functional diversification: the phosphorus-silicon bifunctional comonomer of the present application is a single-molecule three-function structure integrating "unsaturated double bond polymerization site, phosphorus-based flame-retardant functional group, and cage-type siloxane anchoring structure", and a single molecule integrates four core functions of "polymerization crosslinking, interface anchoring, intrinsic flame retardation, and defect plugging", solving the problem of single function of monomer structure in the prior art; Second, eliminating the risk of leakage and fire from the root: the present application completely locks the electrolyte in the three-dimensional network through in-situ crosslinking and solidification, and there is no free liquid electrolyte in the battery cell, completely solving the problems of damage, leakage, burning, and explosion of traditional liquid batteries, and the battery does not catch fire, explode, or leak under the conditions of needle puncture and impact; Third, stabilizing the interface of high-nickel positive electrode and inhibiting the production of gas by side reactions: the composite lithium salt cooperates with the positive electrode coating layer to effectively inhibit the oxygen release and transition metal dissolution of the high-nickel positive electrode, greatly reduces the problem of gas production and bulging during the cycle and high-temperature storage process of the battery cell, and improves the long-term use safety of the battery; Fourth, the present application precisely constructs an asymmetric functional molecular structure of "cage-type siloxane anchoring end-phosphorus oxygen flame-retardant chain segment-acrylic acid polymerization double bond" through an original low-temperature addition grafting synthesis route; relying on the differential polymerization kinetics characteristics of the monomers, a gradient crosslinking network of "interface rigid anchoring, bulk flexible buffering, and overall molecular flame retardation" is formed spontaneously in situ, which can not only effectively stabilize the interface of high-nickel positive electrode and inhibit the metal dissolution and oxygen release side reactions, but also adapt to the 200%-300% super-large volume deformation of silicon-carbon negative electrode, and eliminate the problems of repeated rupture of SEI, growth of lithium dendrites, and gas production of the battery cell, thereby solving the inherent safety contradiction of high-nickel / silicon-carbon system from the molecular root; Fifth, the process of the present application has strong compatibility and is easy to mass-produce: the whole process is solidified at low temperature without damaging the electrode material, and is fully compatible with the existing liquid lithium battery liquid injection and formation production line, without the need for substantial modification of equipment, and can be quickly industrialized, while the energy density of the battery can reach more than 380 Wh / kg, balancing high energy density and high safety.
[0029] The application has the advantages of single-body function diversification, elimination of liquid leakage combustion, inhibition of thermal runaway, stabilization of the positive and negative electrode interface, elimination of lithium dendrite growth conditions, and substantial improvement of the overall safety of high-nickel silicon-carbon system batteries. BRIEF DESCRIPTION OF DRAWINGS
[0030] Figure 1 is the online tracking infrared spectrum diagram of preparation examples 1-5 of the application.
[0031] Figure 2 is the nuclear magnetic resonance hydrogen spectrum diagram of APSA monomer I-APSA monomer V of preparation examples 1-5 of the application.
[0032] Figure 3 is the nuclear magnetic resonance phosphorus spectrum diagram of APSA monomer I-APSA monomer V of preparation examples 1-5 of the application. DETAILED DESCRIPTION
[0033] The specific embodiments of the application will be further described in detail below with reference to the accompanying drawings.
[0034] A phosphorus-silicon bifunctional copolymer monomer is characterized in that its chemical structural formula is as follows: .
[0035] The phosphorus-silicon bifunctional copolymer monomer has a molecular structure of a polymeric group of an acrylic double bond at one end, a phosphorus-oxygen flame-retardant molecular chain grafted at the middle, and a rigid anchoring structure of a cage-shaped siloxane at the end, and is a new single-molecule three-function structure integrating “an unsaturated double bond polymerization site, a phosphorus-based flame-retardant functional group, and a cage-shaped siloxane anchoring structure”.
[0036] A preparation method of a phosphorus-silicon bifunctional copolymer monomer is characterized by comprising the following steps: Step 1: raw material pretreatment: cage-shaped epoxy hemisiloxane (EP-POSS), allyl diethyl phosphate, and hydroxyethyl acrylate are used as reaction raw materials, anhydrous tetrahydrofuran (THF) is used as a reaction solvent, triethylamine is used as an acid-binding agent and a catalyst, and the above raw materials are subjected to water removal treatment; Step 2, low-temperature nucleophilic addition reaction: under nitrogen protection and in an anhydrous and oxygen-free environment, the cage-shaped epoxy hemisiloxane EP-POSS and the allyl diethyl phosphate are added to anhydrous THF solvent, stirred and dissolved in an ice water bath at 0-10℃, triethylamine is slowly added dropwise, and after the dropwise addition is completed, constant temperature reaction is performed for 2h, so that the phosphorus-oxygen functional group is covalently grafted on the surface of the cage-shaped siloxane skeleton to obtain a phosphorus-functionalized POSS intermediate; Third step, end group double bond grafting modification: the reaction system is warmed to 28-35 DEG C, hydroxyethyl acrylate is slowly added dropwise, stirring is continued for 4-6 h, and the hydroxyl group is used for ring opening addition reaction with the epoxy group to connect the acrylic active double bond polymerization site at the end of the molecule to obtain the target crude product with double bond polymerization activity, phosphorus flame retardant and siloxane anchoring; Fourth step, purification and drying: after the reaction is completed, deionized water is used for washing and liquid separation to remove the triethylamine salt byproduct, and the organic phase is collected; THF solvent is removed by rotary evaporation, and then water and impurities are removed by vacuum drying, finally, a light yellow transparent viscous liquid is obtained, which is named as allyl phosphonate cage siloxane acrylate, abbreviated as APSA monomer, and the asymmetric functional molecular structure of "cage siloxane anchoring end-phosphorus oxygen flame retardant segment-acrylic double bond" is precisely constructed through the unique low-temperature addition grafting synthesis route; the four core functions of "polymerization crosslinking, interface anchoring, intrinsic flame retardant and defect plugging" are integrated in a single molecule, relying on the differential polymerization kinetic characteristics of the monomer, the gradient crosslinking network of "interface rigid anchoring, bulk flexible buffering and overall molecular flame retardant" is spontaneously formed in situ, which can not only effectively stabilize the long-term high-nickel positive electrode interface, inhibit metal dissolution and oxygen release side reactions, but also adapt to the 200%-300% ultra-large volume deformation of the silicon-carbon negative electrode, eliminate the problems of repeated SEI rupture, lithium dendrite growth and cell gas production, and solve the inherent safety contradiction of the high-nickel / silicon-carbon system from the molecular root.
[0037] The molar ratio of the cage-type epoxy hemisiloxane (EP-POSS), allyl diethyl phosphate and hydroxyethyl acrylate is 1:(0.9-1.1):(1.05-1.3).
[0038] The content of the anhydrous tetrahydrofuran (THF) is 5-7 times the total mass of the cage-type epoxy hemisiloxane (EP-POSS), allyl diethyl phosphate and hydroxyethyl acrylate.
[0039] The addition amount of the triethylamine is 3%-5% of the total molar amount of the reaction system.
[0040] In the fourth step, the temperature of vacuum drying is 45 DEG C, and the drying time is 12 h.
[0041] The molecular weight of the APSA monomer is 1180-1220 g / mol.
[0042] The APSA monomer has an asymmetric functional structure of "rigid cage siloxane end group-intermediate phosphorus oxygen flame retardant segment-terminal acrylic double bond", and a single molecule has the following functions: ① low-temperature free radical polymerizable acrylic double bond; ② covalently bonded phosphorus flame retardant group; and ③ nanometer cage siloxane interface anchoring structure, which is a special original functional monomer suitable for high-nickel / silicon-carbon systems.
[0043] The following gives a preparation example of the phosphorus-silicon bifunctional comonomer to find the best preparation scheme.
[0044] Preparation Example 1 First step: raw material pretreatment: all raw materials are commercially available products, and T8 type eight glycidyl ether propyl cage type epoxy silsesquioxane (EP-POSS) is selected, the molecular formula of EP-POSS is {(C 11 H 21 O3Si)8O 12} , the number average molecular weight is 1337.88 g / mol, the epoxy equivalent weight is 167, and the purity is ≥99%; with cage type epoxy silsesquioxane (EP-POSS), allyl phosphoric acid diethyl ester, and hydroxyethyl acrylate as the reaction raw materials, anhydrous tetrahydrofuran (THF) as the reaction solvent, and triethylamine as the acid binding agent and catalyst; the molar ratio of EP-POSS, allyl phosphoric acid diethyl ester, and hydroxyethyl acrylate is 1:1.1:1.05, and the addition amount of anhydrous tetrahydrofuran is 5 times the total mass of EP-POSS, allyl phosphoric acid diethyl ester, and hydroxyethyl acrylate; the addition amount of triethylamine is 3%-5% of the total molar amount of all reaction raw materials, preferably 4%; all raw materials are treated for water removal before use: EP-POSS is vacuum dried at 60°C for 8 h, allyl phosphoric acid diethyl ester and hydroxyethyl acrylate are dried by molecular sieves, anhydrous tetrahydrofuran is taken by distillation with sodium wire refluxing water removal, and triethylamine is dried by calcium hydride; Second step: low-temperature nucleophilic addition reaction: build a 250 mL four-necked reaction device, continuously pass high-purity nitrogen into the bottle to replace the air in the bottle for three times, and maintain anhydrous and oxygen-free protective atmosphere with a slight positive pressure of nitrogen throughout the process; weigh 0.01 mol, 13.3788 g of T8 type EP-POSS dried at 60 °C for 8 h to remove water, and 0.011 mol, 2.1360 g of allyl diethyl phosphate dried with molecular sieves to remove water, and put them into a reaction bottle containing 83.6705 g of anhydrous tetrahydrofuran purified by sodium wire reflux distillation; start mechanical stirring, set the speed to 300 r / min, and stabilize the temperature at 5-10 °C in an ice water bath, continuously stir for 30 min until the two solid raw materials are completely dissolved, and the system forms a uniform transparent solution; weigh 0.00126 mol, 0.1275 g of triethylamine dried with calcium hydride to remove water, dilute with 5 mL of anhydrous tetrahydrofuran, and then transfer it to a constant-pressure dropping funnel, and slowly drop at a uniform speed for 30 min, and control the temperature in real time during the whole dropping process to ensure that the temperature of the reaction system does not exceed 10 °C; after the dropping operation is completed, keep the ice water bath at 5-10 °C constant temperature and continue to stir for 2 h. During the reaction, the phosphorus-oxygen functional groups undergo ring-opening nucleophilic addition with the epoxy groups on the surface of EP-POSS, realizing the covalent grafting of phosphorus-oxygen functional groups on the surface of the cage siloxane skeleton. After the reaction is completed, a clear and uniform phosphorus-functionalized POSS intermediate is obtained. Third step: end group double bond grafting modification: remove the ice water bath device, and warm the reaction system to 28 °C, and keep the system temperature uniform and stable for 10 min; weigh 0.0105 mol, 1.2193 g of hydroxyethyl acrylate treated by molecular sieves to remove water deeply, transfer it to a constant-pressure dropping funnel, and drop at a uniform speed for 40 min, and keep the stirring speed at 300 r / min throughout the process; after the dropping is completed, control the system temperature to maintain 25-30 °C for continuous stirring reaction for 4-6 h, and the preferred reaction time is 5 h; during the reaction, the hydroxyl groups in the hydroxyethyl acrylate molecules undergo ring-opening addition reaction with the residual epoxy groups of the phosphorus-functionalized POSS intermediate, and the acrylic active double bond polymerization site is stably introduced at the molecular end; the whole reaction process is tracked and monitored by Fourier infrared spectroscopy, and the reaction endpoint is reached when the characteristic absorption peak of the epoxy group at 910 cm⁻¹ basically disappears; after the reaction is completed, the target crude product is obtained, which has a polymerizable acrylic double bond, a covalently bonded phosphorus-oxygen flame-retardant chain segment, and a cage siloxane rigid anchoring structure; Fourth step: purification and drying: after the above-mentioned crude product reaction system is naturally cooled to room temperature, the whole reaction liquid is transferred to a 250 mL separation funnel, an equal volume of deionized water is added for shaking washing, after standing and separating, the lower layer of the water phase containing the by-product of triethylamine hydrochloride is discarded, the water washing and separation operation is repeated 3 times until the pH value of the water phase is close to neutral, the triethylamine salt by-product in the system is completely removed, and the upper layer of the light yellow organic phase is collected; anhydrous magnesium sulfate powder is added to the obtained organic phase and is placed for drying for 2 h to remove trace water, and the solid drying agent is filtered to obtain a clear organic filtrate; the filtrate is moved into a rotary evaporator, the temperature is set to 40 °C, the vacuum degree is -0.08 MPa, and the system is reduced pressure rotary evaporated to completely remove the anhydrous tetrahydrofuran solvent in the system; the viscous crude product obtained by rotary evaporation is transferred into a vacuum drying box, and is constant-temperature vacuum dried at 45 °C and a vacuum degree of -0.095 MPa for 12 h to deeply remove residual trace solvents and moisture impurities; after drying is completed, the product is cooled to room temperature and discharged, and finally a light yellow transparent viscous liquid product is obtained, which is called APSA monomer I.
[0045] Preparation example 2: First step: raw material pretreatment: the raw materials are all commercially available products, and T8 type eight glycidyl ether propyl cage type epoxy silsesquioxane (EP-POSS) is selected, the molecular formula of EP-POSS is {(C 11 H 21 O3Si)8O 12} , the number average molecular weight is 1337.88 g / mol, the epoxy equivalent is 167, and the purity is ≥99%; with EP-POSS, allyl phosphoric acid diethyl ester and hydroxyethyl acrylate as the reaction raw materials, anhydrous tetrahydrofuran (THF) as the reaction solvent, and triethylamine as the acid binding agent and catalyst; the molar ratio of EP-POSS, allyl phosphoric acid diethyl ester and hydroxyethyl acrylate is 1:1.1:1.05, the addition amount of anhydrous tetrahydrofuran is 5 times the total mass of EP-POSS, allyl phosphoric acid diethyl ester and hydroxyethyl acrylate, the addition amount of triethylamine is 3%-5% of the total molar amount of all reaction raw materials, and preferably 4%; all raw materials are treated by water removal before use: EP-POSS is vacuum dried at 60 °C for 8 h, allyl phosphoric acid diethyl ester and hydroxyethyl acrylate are dried by molecular sieves, anhydrous tetrahydrofuran is taken by distillation after sodium wire refluxing water removal, and triethylamine is dried by calcium hydride; Step 2: Low-temperature nucleophilic addition reaction: A 250 mL four-necked reaction apparatus was constructed. High-purity nitrogen was continuously introduced three times to replace the air in the flask, maintaining a slightly positive nitrogen pressure and an anhydrous and oxygen-free protective atmosphere throughout the process. 0.01 mol (13.3788 g) of T8-type EP-POSS, dried under vacuum at 60 °C for 8 h to remove water, and 0.011 mol (2.1360 g) of allyl phosphate, dried under molecular sieves to remove water, were weighed and added to a reaction flask containing 83.6705 g of anhydrous tetrahydrofuran purified by sodium wire reflux distillation. Mechanical stirring was started at 300 r / min, and the temperature was stabilized at 0–5 °C in an ice-water bath. Stirring continued for 30 min until both solid raw materials were completely dissolved, forming a homogeneous and transparent solution. 0.00126 mol (0.1275 g) of triethylamine, dried under calcium hydride to remove water, was weighed and reacted with 5 mL of... Anhydrous tetrahydrofuran was diluted and transferred to a constant pressure dropping funnel. It was added slowly and uniformly for 30 min, with the temperature controlled in real time throughout the process to ensure that the temperature of the reaction system did not exceed 5 °C. After the addition was completed, the reaction was carried out at a constant temperature of 0-5 °C in an ice-water bath for 2 h with stirring. During the reaction, the phosphorus-oxygen functional groups underwent ring-opening nucleophilic addition with the epoxy groups on the surface of EP-POSS, realizing the covalent grafting of phosphorus-oxygen functional groups onto the surface of the cage-like siloxane framework. After the reaction was completed, a clear and homogeneous phosphorus-functionalized POSS intermediate was obtained. Step 3: End-group double bond grafting modification: Remove the ice-water bath device, heat the reaction system to 28 ℃, and keep it at this temperature for 10 min to ensure the system temperature is uniform and stable; weigh 0.0105 mol and 1.2193 g of hydroxyethyl acrylate that has undergone deep dehydration treatment with molecular sieves, transfer it to a constant pressure dropping funnel, and add it dropwise at a uniform and slow rate for 40 min, maintaining a stirring speed of 300 r / min throughout the process; after the addition is complete, control the system temperature to maintain 25–30 ℃ and continue stirring for 4–6 h, with a preferred reaction time of 5 h; during the reaction, the hydroxyl groups in the hydroxyethyl acrylate molecule undergo a ring-opening addition reaction with the epoxy groups remaining in the phosphorus-functionalized POSS intermediate, stably attaching to the active double bond polymerization site of acrylic acid at the molecule end. The entire reaction is monitored using Fourier transform infrared spectroscopy, and the reaction is carried out when the epoxy groups reach 910 cm⁻¹. The reaction ends when the characteristic absorption peaks basically disappear; after the reaction, the target crude product is obtained, which simultaneously possesses polymerizable acrylic double bonds, covalently bonded phosphorus-oxygen flame-retardant segments, and cage-type siloxane rigid anchoring structure. Step 4: Purification and Drying: After the above crude product reaction system has cooled naturally to room temperature, transfer all the reaction solution to a 250 mL separatory funnel, add an equal volume of deionized water, and shake and wash. After standing and separating the layers, discard the lower aqueous phase containing triethylamine hydrochloride byproducts. Repeat the water washing and separation operation 3 times until the pH of the aqueous phase is close to neutral, thus completely removing the triethylamine salt byproducts in the system. Collect the upper pale yellow organic phase. Add anhydrous magnesium sulfate powder to the obtained organic phase and let it stand and dry for 2 hours to remove trace amounts of water. Filter to remove the solid desiccant to obtain a clear organic filtrate. Transfer the filtrate to a rotary evaporator and set the temperature to 40 ℃ and the vacuum degree to -0.08 MPa for reduced pressure rotary evaporation to completely remove the anhydrous tetrahydrofuran solvent in the system. Transfer the viscous crude product obtained by rotary evaporation to a vacuum drying oven at 45 ℃ and a vacuum degree of -0.095 MPa. Under constant temperature vacuum drying conditions for 12 hours, residual trace amounts of solvent and moisture impurities are thoroughly removed; after drying is completed, the product is cooled to room temperature and discharged, finally yielding a light yellow transparent viscous liquid product, which is called APSA monomer II.
[0046] Preparation Example 3: Step 1: Raw Material Pretreatment: All raw materials are commercially available products, using T8 type octaglycidyl ether propyl cage-type epoxy silsesquioxane (EP-POSS). EP-POSS molecular formula {(C 11 H 21 O3Si)8O 12} The number-average molecular weight is 1337.88 g / mol, the epoxy equivalent is 167, and the purity is ≥99%. The reaction raw materials are cage-type epoxy silsesquioxane (EP-POSS), allyl phosphate diethyl ester, and hydroxyethyl acrylate; the reaction solvent is anhydrous tetrahydrofuran (THF); and triethylamine is used as an acid-binding agent and catalyst. The molar ratio of EP-POSS, allyl phosphate diethyl ester, and hydroxyethyl acrylate is 1:1.1:1.05. The amount of anhydrous tetrahydrofuran added is 5 times the total mass of EP-POSS, allyl phosphate diethyl ester, and hydroxyethyl acrylate. The amount of triethylamine added is 3%–5% of the total molar mass of all reaction raw materials, preferably 4%. All raw materials are dehydrated before use: EP-POSS is vacuum dried at 60℃ for 8 h; allyl phosphate diethyl ester and hydroxyethyl acrylate are dried using molecular sieves; anhydrous tetrahydrofuran is dehydrated by reflux with sodium wire and distilled; and triethylamine is dehydrated by drying with calcium hydride. Step 2: Low-temperature nucleophilic addition reaction: A 250 mL four-necked reaction apparatus was constructed. High-purity nitrogen was continuously introduced three times to replace the air in the flask, maintaining a slightly positive nitrogen pressure and an anhydrous and oxygen-free protective atmosphere throughout the process. 0.01 mol (13.3788 g) of T8-type EP-POSS, dried under vacuum at 60 °C for 8 h to remove water, and 0.011 mol (2.1360 g) of allyl phosphate, dried under molecular sieves to remove water, were weighed and added to a reaction flask containing 83.6705 g of anhydrous tetrahydrofuran purified by sodium wire reflux distillation. Mechanical stirring was started at 300 r / min, and the temperature was stabilized at 0–5 °C in an ice-water bath. Stirring continued for 30 min until both solid raw materials were completely dissolved, forming a homogeneous and transparent solution. 0.00126 mol (0.1275 g) of triethylamine, dried under calcium hydride to remove water, was weighed and reacted with 5 mL of... Anhydrous tetrahydrofuran was diluted and transferred to a constant pressure dropping funnel. It was added slowly and uniformly for 30 min, with the temperature controlled in real time throughout the process to ensure that the temperature of the reaction system did not exceed 5 °C. After the addition was completed, the reaction was carried out at a constant temperature of 0-5 °C in an ice-water bath for 2 h with stirring. During the reaction, the phosphorus-oxygen functional groups underwent ring-opening nucleophilic addition with the epoxy groups on the surface of EP-POSS, realizing the covalent grafting of phosphorus-oxygen functional groups onto the surface of the cage-like siloxane framework. After the reaction was completed, a clear and homogeneous phosphorus-functionalized POSS intermediate was obtained. Step 3: End-group double bond grafting modification: Remove the ice-water bath device, heat the reaction system to 35℃, and keep it at this temperature for 10 min to ensure the system temperature is uniform and stable; weigh 0.0105 mol and 1.2193 g of hydroxyethyl acrylate that has undergone deep dehydration treatment with molecular sieves, transfer it to a constant pressure dropping funnel, and add it dropwise at a uniform rate for 40 min, maintaining a stirring speed of 300 r / min throughout the process; after the addition is complete, control the system temperature to maintain 25–30℃ and continue stirring for 4–6 h, with a preferred reaction time of 5 h; during the reaction, the hydroxyl groups in the hydroxyethyl acrylate molecule undergo a ring-opening addition reaction with the epoxy groups remaining in the phosphorus-functionalized POSS intermediate, stably attaching to the active double bond polymerization site of acrylic acid at the molecule end. The entire reaction is monitored using Fourier transform infrared spectroscopy, and the reaction is stopped when the epoxy groups reach 910 cm⁻¹. The reaction ends when the characteristic absorption peaks basically disappear; after the reaction, the target crude product is obtained, which simultaneously possesses polymerizable acrylic double bonds, covalently bonded phosphorus-oxygen flame-retardant segments, and cage-type siloxane rigid anchoring structure. Step 4: Purification and Drying: After the above crude product reaction system has cooled naturally to room temperature, transfer all the reaction solution to a 250 mL separatory funnel, add an equal volume of deionized water, and shake and wash. After standing and separating the layers, discard the lower aqueous phase containing triethylamine hydrochloride byproducts. Repeat the water washing and separation operation 3 times until the pH of the aqueous phase is close to neutral, thus completely removing the triethylamine salt byproducts in the system. Collect the upper pale yellow organic phase. Add anhydrous magnesium sulfate powder to the obtained organic phase and let it stand and dry for 2 hours to remove trace amounts of water. Filter to remove the solid desiccant to obtain a clear organic filtrate. Transfer the filtrate to a rotary evaporator and set the temperature to 40 ℃ and the vacuum degree to -0.08 MPa for reduced pressure rotary evaporation to completely remove the anhydrous tetrahydrofuran solvent in the system. Transfer the viscous crude product obtained by rotary evaporation to a vacuum drying oven at 45 ℃ and a vacuum degree of -0.095 MPa. Under constant temperature vacuum drying conditions for 12 hours, residual trace solvents and moisture impurities are thoroughly removed; after drying is completed, the product is cooled to room temperature and discharged, finally yielding a light yellow transparent viscous liquid product, which is called APSA monomer III.
[0047] Preparation Example 4: Step 1: Raw Material Pretreatment: All raw materials are commercially available products, using T8 type octaglycidyl ether propyl cage-type epoxy silsesquioxane (EP-POSS). EP-POSS molecular formula {(C 11 H 21 O3Si)8O 12} The number-average molecular weight is 1337.88 g / mol, the epoxy equivalent is 167, and the purity is ≥99%. The reaction raw materials are cage-type epoxy silsesquioxane (EP-POSS), allyl phosphate diethyl ester, and hydroxyethyl acrylate; the reaction solvent is anhydrous tetrahydrofuran (THF); and triethylamine is used as an acid-binding agent and catalyst. The molar ratio of EP-POSS, allyl phosphate diethyl ester, and hydroxyethyl acrylate is 1:0.9:1.05. The amount of anhydrous tetrahydrofuran added is 5 times the total mass of EP-POSS, allyl phosphate diethyl ester, and hydroxyethyl acrylate. The amount of triethylamine added is 3%–5% of the total molar mass of all reaction raw materials, preferably 4%. All raw materials are dehydrated before use: EP-POSS is vacuum dried at 60℃ for 8 h; allyl phosphate diethyl ester and hydroxyethyl acrylate are dried using molecular sieves; anhydrous tetrahydrofuran is dehydrated by reflux with sodium wire and distilled; and triethylamine is dehydrated by drying with calcium hydride. Step 2: Low-temperature nucleophilic addition reaction: A 250 mL four-necked reaction apparatus was constructed. High-purity nitrogen was continuously introduced three times to replace the air in the flask, maintaining a slightly positive nitrogen pressure and an anhydrous and oxygen-free protective atmosphere throughout the process. 0.01 mol (13.3788 g) of T8-type EP-POSS, dried under vacuum at 60 °C for 8 h to remove water, and 0.009 mol (1.17476 g) of allyl phosphate, dried under molecular sieves to remove water, were weighed and added to a reaction flask containing 83.6705 g of anhydrous tetrahydrofuran purified by sodium wire reflux distillation. Mechanical stirring was started at 300 r / min, and the temperature was stabilized at 0–5 °C in an ice-water bath. Stirring continued for 30 min until both solid raw materials were completely dissolved, forming a homogeneous and transparent solution. 0.00126 mol (0.1275 g) of triethylamine, dried under calcium hydride to remove water, was weighed and reacted with 5 mL of... Anhydrous tetrahydrofuran was diluted and transferred to a constant pressure dropping funnel. It was added slowly and uniformly for 30 min, with the temperature controlled in real time throughout the process to ensure that the temperature of the reaction system did not exceed 5 °C. After the addition was completed, the reaction was carried out at a constant temperature of 0-5 °C in an ice-water bath for 2 h with stirring. During the reaction, the phosphorus-oxygen functional groups underwent ring-opening nucleophilic addition with the epoxy groups on the surface of EP-POSS, realizing the covalent grafting of phosphorus-oxygen functional groups onto the surface of the cage-like siloxane framework. After the reaction was completed, a clear and homogeneous phosphorus-functionalized POSS intermediate was obtained. Step 3: End-group double bond grafting modification: Remove the ice-water bath device, heat the reaction system to 28 ℃, and keep it at this temperature for 10 min to ensure the system temperature is uniform and stable; weigh 0.0105 mol and 1.2193 g of hydroxyethyl acrylate that has undergone deep dehydration treatment with molecular sieves, transfer it to a constant pressure dropping funnel, and add it dropwise at a uniform and slow rate for 40 min, maintaining a stirring speed of 300 r / min throughout the process; after the addition is complete, control the system temperature to maintain 25–30 ℃ and continue stirring for 4–6 h, with a preferred reaction time of 5 h; during the reaction, the hydroxyl groups in the hydroxyethyl acrylate molecule undergo a ring-opening addition reaction with the epoxy groups remaining in the phosphorus-functionalized POSS intermediate, stably attaching to the active double bond polymerization site of acrylic acid at the molecule end. The entire reaction is monitored using Fourier transform infrared spectroscopy, and the reaction is carried out when the epoxy groups reach 910 cm⁻¹. The reaction ends when the characteristic absorption peaks basically disappear; after the reaction, the target crude product is obtained, which simultaneously possesses polymerizable acrylic double bonds, covalently bonded phosphorus-oxygen flame-retardant segments, and cage-type siloxane rigid anchoring structure. Step 4: Purification and Drying: After the above crude product reaction system has cooled naturally to room temperature, transfer all the reaction solution to a 250 mL separatory funnel, add an equal volume of deionized water, and shake and wash. After standing and separating the layers, discard the lower aqueous phase containing triethylamine hydrochloride byproducts. Repeat the water washing and separation operation 3 times until the pH of the aqueous phase is close to neutral, thus completely removing the triethylamine salt byproducts in the system. Collect the upper pale yellow organic phase. Add anhydrous magnesium sulfate powder to the obtained organic phase and let it stand and dry for 2 hours to remove trace amounts of water. Filter to remove the solid desiccant to obtain a clear organic filtrate. Transfer the filtrate to a rotary evaporator and set the temperature to 40 ℃ and the vacuum degree to -0.08 MPa for reduced pressure rotary evaporation to completely remove the anhydrous tetrahydrofuran solvent in the system. Transfer the viscous crude product obtained by rotary evaporation to a vacuum drying oven at 45 ℃ and a vacuum degree of -0.095 MPa. Under constant temperature vacuum drying conditions for 12 hours, residual trace amounts of solvent and moisture impurities are thoroughly removed; after drying is completed, the product is cooled to room temperature and discharged, finally yielding a light yellow transparent viscous liquid product, which is called APSA monomer IV.
[0048] Preparation Example 5: Step 1: Raw Material Pretreatment: All raw materials are commercially available products, using T8 type octaglycidyl ether propyl cage-type epoxy silsesquioxane (EP-POSS). EP-POSS molecular formula {(C 11 H 21 O3Si)8O 12} The number-average molecular weight is 1337.88 g / mol, the epoxy equivalent is 167, and the purity is ≥99%. The reaction raw materials are cage-type epoxy silsesquioxane (EP-POSS), allyl phosphate diethyl ester, and hydroxyethyl acrylate; the reaction solvent is anhydrous tetrahydrofuran (THF); and triethylamine is used as an acid-binding agent and catalyst. The molar ratio of EP-POSS, allyl phosphate diethyl ester, and hydroxyethyl acrylate is 1:1.1:1.3. The amount of anhydrous tetrahydrofuran added is 5 times the total mass of EP-POSS, allyl phosphate diethyl ester, and hydroxyethyl acrylate. The amount of triethylamine added is 3%–5% of the total molar mass of all reaction raw materials, preferably 4%. All raw materials are dehydrated before use: EP-POSS is vacuum dried at 60℃ for 8 h; allyl phosphate diethyl ester and hydroxyethyl acrylate are dried using molecular sieves; anhydrous tetrahydrofuran is dehydrated by reflux with sodium wire and distilled; and triethylamine is dehydrated by drying with calcium hydride. Step 2: Low-temperature nucleophilic addition reaction: A 250 mL four-necked reaction apparatus was constructed. High-purity nitrogen was continuously introduced three times to replace the air in the flask, maintaining a slightly positive nitrogen pressure and an anhydrous and oxygen-free protective atmosphere throughout the process. 0.01 mol (13.3788 g) of T8-type EP-POSS, dried under vacuum at 60 °C for 8 h to remove water, and 0.011 mol (2.1360 g) of allyl phosphate, dried under molecular sieves to remove water, were weighed and added to a reaction flask containing 83.6705 g of anhydrous tetrahydrofuran purified by sodium wire reflux distillation. Mechanical stirring was started at 300 r / min, and the temperature was stabilized at 0–5 °C in an ice-water bath. Stirring continued for 30 min until both solid raw materials were completely dissolved, forming a homogeneous and transparent solution. 0.00126 mol (0.1275 g) of triethylamine, dried under calcium hydride to remove water, was weighed and reacted with 5 mL of... Anhydrous tetrahydrofuran was diluted and transferred to a constant pressure dropping funnel. It was added slowly and uniformly for 30 min, with the temperature controlled in real time throughout the process to ensure that the temperature of the reaction system did not exceed 5 °C. After the addition was completed, the reaction was carried out at a constant temperature of 0-5 °C in an ice-water bath for 2 h with stirring. During the reaction, the phosphorus-oxygen functional groups underwent ring-opening nucleophilic addition with the epoxy groups on the surface of EP-POSS, realizing the covalent grafting of phosphorus-oxygen functional groups onto the surface of the cage-like siloxane framework. After the reaction was completed, a clear and homogeneous phosphorus-functionalized POSS intermediate was obtained. Step 3: Terminal Double Bond Grafting Modification: Remove the ice-water bath and heat the reaction system to 28 ℃, keeping it at this temperature for 10 min to ensure a uniform and stable temperature. Weigh 0.013 mol (1.5096 g) of hydroxyethyl acrylate that has undergone deep dehydration treatment using molecular sieves, transfer it to a constant-pressure dropping funnel, and slowly add it dropwise over 40 min, maintaining a stirring speed of 300 r / min throughout. After the addition is complete, maintain the system temperature at 25–30 ℃ and continue stirring for 4–6 h, with a preferred reaction time of 5 h. During the reaction, the hydroxyl groups in the hydroxyethyl acrylate molecule undergo a ring-opening addition reaction with the residual epoxy groups in the phosphorus-functionalized POSS intermediate, stably attaching to the active double bond polymerization site of acrylic acid at the molecule's end. The entire reaction is monitored using Fourier transform infrared spectroscopy. When the epoxy groups reach 910 cm⁻¹... The reaction ends when the characteristic absorption peaks basically disappear; after the reaction, the target crude product is obtained, which simultaneously possesses polymerizable acrylic double bonds, covalently bonded phosphorus-oxygen flame-retardant segments, and cage-type siloxane rigid anchoring structure. Step 4: Purification and Drying: After the above crude product reaction system has cooled naturally to room temperature, transfer all the reaction solution to a 250 mL separatory funnel, add an equal volume of deionized water, and shake and wash. After standing and separating the layers, discard the lower aqueous phase containing triethylamine hydrochloride byproducts. Repeat the water washing and separation operation 3 times until the pH of the aqueous phase is close to neutral, thus completely removing the triethylamine salt byproducts in the system. Collect the upper pale yellow organic phase. Add anhydrous magnesium sulfate powder to the obtained organic phase and let it stand and dry for 2 hours to remove trace amounts of water. Filter to remove the solid desiccant to obtain a clear organic filtrate. Transfer the filtrate to a rotary evaporator and set the temperature to 40 ℃ and the vacuum degree to -0.08 MPa for reduced pressure rotary evaporation to completely remove the anhydrous tetrahydrofuran solvent in the system. Transfer the viscous crude product obtained by rotary evaporation to a vacuum drying oven at 45 ℃ and a vacuum degree of -0.095 MPa. Under constant temperature vacuum drying conditions for 12 hours, residual trace amounts of solvent and moisture impurities are thoroughly removed; after drying is completed, the product is cooled to room temperature and discharged, finally yielding a light yellow transparent viscous liquid product, called APSA monomer V.
[0049] The following tests were performed on the preparation examples 1-5 above: (1) Molecular weight detection: The number-average molecular weight of APSA monomers in Preparation Examples 1-5 was determined by gel permeation chromatography (GPC). Taking APSA monomer I prepared in Preparation Example 1 as an example: the mobile phase was anhydrous tetrahydrofuran, and a standard curve was established using narrow-distribution polystyrene standard. Before testing, 0.1 g of APSA monomer I was dissolved in 10 mL of anhydrous THF, filtered through a 0.22 μm organic filter membrane, and fully dissolved by ultrasonication before being loaded onto the instrument to collect the elution curve. The software automatically fitted the curve to obtain the Mn and molecular weight distribution index PD for preparation example 1. Other preparation examples followed the same method. The APSA molecule of this invention is prepared from T8 type octagylic acid propyl cage-type epoxy silsesquioxane via a two-step ring-opening grafting process with allyl phosphate diethyl ester and hydroxyethyl acrylate. The theoretical molecular weight is calculated to be 1196.88 g / mol, and this invention limits the acceptable molecular weight range to 1180–1220 g / mol. The APSA monomer I obtained in Preparation Example 1 was tested by GPC and had a number-average molecular weight Mn=1172 g / mol and PDI=1.36. The molecular weight was lower than the lower limit of 1180 g. The reason is that the low temperature reaction range is too high, the epoxy ring-opening reaction is incomplete, the system has residual ungrafted phosphate ester small molecules, and the low molecular weight impurity peaks are obvious, which does not meet the molecular weight requirements of this invention. The APSA monomer II obtained in Preparation 2 was tested by GPC and showed a number-average molecular weight Mn = 1196 g / mol, PDI = 1.12, and the elution curve showed a single symmetrical narrow peak. There were no free raw materials or polymerization byproducts, and the molecular weight fell entirely within the standard range of 1180–1220 g / mol, indicating a complete molecular structure. The APSA monomer III obtained in Preparation 3 was tested by GPC and showed a number-average molecular weight Mn = 1245 g / mol, PDI = 1.42. The measured molecular weight exceeded the upper limit of 1220 g, indicating the presence of a large number of high molecular weight polymerization impurities. This was because the temperature in the heating section was too high, causing intermolecular self-polymerization of the acrylic acid double bonds. The APSA monomer IV obtained in preparation step 4 was tested by GPC and the number average molecular weight Mn was 1165 g / mol. The reason was that the ratio of allyl phosphate diethyl ester was insufficient and a large number of phosphorus oxygen segments were not grafted onto the silicon skeleton. The measured value was lower than the lower limit of the pass. The APSA monomer V obtained in preparation step 5 was tested by GPC and the number average molecular weight Mn was 1228 g / mol. The reason is that the excess hydroxyethyl acrylate caused the excess monomer to undergo self-polymerization to form dimer impurities, which slightly exceeded the upper limit of molecular weight and the impurity content of the product was too high.
[0050] (2) Infrared spectroscopy analysis: The reaction processes of Preparation Examples 1-5 were monitored using Fourier transform infrared spectroscopy. The infrared spectra of Preparation Examples 1-5 are shown below: Online tracking and detection were carried out using a Fourier transform infrared spectrometer equipped with an attenuated total reflectance (ATR) probe. Before testing, the entire instrument was powered on and preheated for 30 minutes to ensure that the infrared light source, interferometer, and detector reached steady-state operating conditions. The ATR crystal was cleaned and the sample chamber was sealed. The background of the air substrate was scanned first, and then the spectrum of the anhydrous tetrahydrofuran solvent was scanned separately, with double subtraction of infrared absorption interference from water vapor, CO2, and solvent. The scanning wavenumber range was set to 500–4000 cm⁻¹, the resolution to 4 cm⁻¹, and 32 single cumulative scans, with a data acquisition interval of 15 minutes. Throughout the test, the reaction vessel was kept under nitrogen protection to prevent water and oxygen deprivation. The dry and impurity-free ATR probe was completely immersed below the surface of the reaction liquid, avoiding obstruction from the stir bar and the vessel wall. The original interference signal was continuously and automatically acquired from the start of the low-temperature addition reaction until the end of the double bond grafting reaction. The instrument performed Fourier transform in real time to generate the infrared transmission spectrum at the corresponding moment, and the real-time process parameters such as temperature and reaction time of each embodiment were recorded simultaneously.
[0051] Infrared spectra of each preparation example at different time points were read one by one to locate the characteristic absorption peaks of key functional groups: 910 cm⁻¹ is the characteristic peak of epoxy group, 1090 cm⁻¹ is the broad peak of Si-O-Si cage silicon framework, 1260 cm⁻¹ is the peak of P=O phosphorus oxygen bond, 1726 cm⁻¹ is the peak of acrylate carbonyl group, and 1632 cm⁻¹ is the peak of acrylic acid C=C double bond. The progress of the ring-opening reaction was judged by the degree of decay of the 910 cm⁻¹ epoxy peak. When the epoxy peak continued to weaken and disappeared completely as the reaction progressed, and the characteristic peaks of phosphorus oxygen, siloxane, and acrylic acid double bond appeared synchronously and stably and their intensities no longer changed, the reaction was determined to be complete. The peak intensity change rate and the number of residual impurity peaks of preparation examples 1 to 5 were compared to quantitatively distinguish the effects of different temperature control ranges and raw material ratios on epoxy ring-opening efficiency and side reaction generation, and the optimal synthesis process conditions were screened. As attached Figure 1 The online tracking infrared spectra of Preparation Examples 1-5 were used as the core criteria for judgment, with the 910 cm⁻¹ epoxy peak, 1260 cm⁻¹ phosphorus-oxygen peak, and 1632 cm⁻¹ acrylic acid double bond peak as the core criteria: In the optimal preparation example 2, the epoxy characteristic peak completely disappeared, and the absorption peaks of each target functional group were complete and regular, without impurity absorption bands; In Preparation Example 1, the low temperature was too high, and the spectrum showed weak residual epoxy absorption, and the phosphorus-oxygen peak intensity was low, indicating incomplete epoxy ring-opening conversion; In Preparation Example 3, the heating temperature was too high, and the acrylic acid double bond peak was significantly attenuated and new impurity absorption was added, indicating high-temperature self-polymerization of double bonds to generate byproducts; In Preparation Example 4, the phosphate ester feed was insufficient, and the intensity of the P=O characteristic peak was the lowest among the five groups, indicating insufficient grafting of phosphorus functional structures; In Preparation Example 5, the hydroxyethyl acrylate was excessive, and the spectrum showed a broad peak characteristic of acrylic acid self-polymerization impurities, with significant small molecule residues. The infrared results directly reflected the differences in the degree of epoxy ring-opening and side reactions in each group.
[0052] (3) The APSA monomers I-V from Preparation Examples 1 to 5 were detected by Fourier transform nuclear magnetic resonance spectroscopy. The proton and phosphorus nuclear magnetic resonance spectra of APSA monomers I-V are as follows: I. Sample Pretreatment Section: Take 10 mg each of the purified and dried APSA monomers I to V from each preparation example, place them in a clean NMR sample tube, add 0.6 mL of deuterated chloroform (CDCl3), and shake thoroughly until the monomers are completely dissolved and the solution is clear and free of suspended impurities. Add tetramethylsilane (TMS) to the sample tube as an internal standard to calibrate the chemical shift, seal the sample tube opening to prevent moisture, and let it stand for 5 min to remove tiny air bubbles in the solution. The NMR sample preparation is now complete. The five groups of monomers were prepared in parallel to prepare the corresponding test samples. II. Instrument Operation Section: After the NMR spectrometer was powered on and kept at a constant temperature for 2 hours, sample tubes containing APSA monomers I to V were sequentially inserted into the NMR probe. ¹H NMR testing was performed first, with the proton spectrum scanning pulse sequence set, 64 scans, and a chemical shift acquisition range of 0–10 ppm. The raw proton spectrum data was saved after acquisition. Then, ³¹P NMR detection was performed using a different test channel, with 128 phosphorus spectrum scans and a chemical shift acquisition range of 0–10 ppm. The instrument automatically locked and shimmed the field throughout the process to ensure peak resolution. The proton and phosphorus spectrum signals for the five monomers were acquired sequentially, and the raw data were Fourier transformed to generate standard NMR spectra. III. Data Analysis Section: The chemical shifts of each group of spectra were calibrated using the TMS signal zero point. The peak shape and peak area of the three characteristic peaks in ¹H-NMR (δ0.8~1.0 ppm for silane hydrogen, δ4.0~4.8 ppm for phosphoester methylene hydrogen, and δ5.8~6.4 ppm for acrylic acid double bond protons) were analyzed. The characteristic main peak of phosphoester at δ7.6 ppm in ³¹P-NMR was analyzed, and the content of free phosphoester impurities in the system was determined by the number of impurity peaks in the phospho-NMR spectrum. The integrity of the NMR peaks and the intensity of impurity side peaks in preparation examples 1~5 were compared to determine the differences in monomer grafting integrity and by-product content under different synthesis processes. As attached Figure 2 and attached Figure 3 Combining Preparation Examples 1-5, the ¹H-NMR and ³¹P-NMR spectra of the five sets of products were analyzed simultaneously. In Preparation Example 2, the ¹H spectrum showed only three sets of symmetrical and sharp characteristic peaks: silane, phosphoester methylene, and acrylic acid double bonds. The peak areas matched the theoretical molecular ratio. In its ³¹P-NMR, only a single main peak appeared at δ7.6 ppm, with no free phosphorus-containing impurity peaks, and the molecular structure was uniform and complete. In Preparation Example 1, the ¹H spectrum showed unreacted EP-POSS impurity peaks, and the phosphorus spectrum showed trace phosphorus decomposition shoulder peaks. In Preparation Example 3, the ¹H spectrum showed a significant decrease in double bond signal and the appearance of a diffuse broad peak of polymer polymerization. In Preparation Example 4, the intensity of the ¹H peak corresponding to the phosphoester and the main peak of the phosphorus spectrum were significantly lower. In Preparation Example 5, the ¹H spectrum showed additional free hydroxyethyl acrylate dimer impurity peaks, and the phosphorus spectrum showed no obvious deterioration. The NMR data accurately distinguished the grafting integrity and impurity types of each set of silane cage framework, phosphorus oxygen segment, and double bond groups. Based on the above test results: The infrared transmittance spectrum detected three characteristic absorption valleys: 2920 cm⁻¹ alkyl CH, 1090 cm⁻¹ broad Si-O-Si cage silicon framework, 1260 cm⁻¹ P=O phosphorus-oxygen bond, 1726 cm⁻¹ acrylic acid C=O, and 1632 cm⁻¹ C=C double bond. Simultaneously, no characteristic peaks of the epoxy raw material were detected, confirming that EP-POSS epoxy is completely ring-opened and grafted with phospholipid and acrylic acid groups. ¹H-NMR: The three sets of signals—δ0.8~1.0 ppm for silane, δ4.0~4.8 ppm for phosphoester-linked methylene, and δ5.8~6.4 ppm for protons in acrylic acid double bonds—correspond one-to-one with the infrared functional groups. The presence of a single sharp main peak at δ7.6 ppm in ³¹P-NMR indicates that the phospholipid molecules are covalently bonded to the silica cage framework and there are no free small molecule phospholipid impurities.
[0053] The APSA monomers I-V from Preparation Examples 1-5 were analyzed and calculated, as shown in Table 1 below. Table 1 lists the product yields, total impurity content, major side reactions, and product characteristics of APSA monomers I-V. Table 1. Product yields, total impurity content, major side reactions, and product characteristics of APSA monomers I through V. Where: Product yield = (Actual mass of purified APSA monomer obtained ÷ Theoretical mass of APSA monomer produced) × 100% Total impurity content = (Total mass of all impurities in the system ÷ Total mass of purified APSA product) × 100% A comparison of Preparation Example 1 and Preparation Example 3 with Preparation Example 2 shows that decomposition and self-polymerization side reactions are triggered when the low temperature range exceeds 0-5℃ and the heating range exceeds 28℃, resulting in a significant decrease in yield and a substantial increase in impurities. Comparing Preparation Example 4 and Preparation Example 5 with Preparation Example 2, it can be seen that insufficient phosphate ester leads to the absence of flame retardant structure, and excessive hydroxyethyl acrylate causes self-polymerization impurities. Obviously, the molar ratio of 1:1.1:1.05 in Preparation Example 2 is the optimal ratio. The product yield of Preparation Example 2 is the highest among Preparation Examples 1-5, and the total impurity content is the lowest. Therefore, Preparation Example 2 is the optimal scheme for the preparation of phosphorus-silicon bifunctional comonomers. Preparation Example 2 achieves the fewest side reactions, the highest yield, and the lowest impurities by using segmented precise temperature control and standard molar ratio. The monomer molecular structure is complete and can be directly used in the subsequent in-situ polymerization system for semi-solid batteries.
[0054] Major side reactions and products: By identifying the types of byproducts based on GPC chromatographic peak assignments: 1) Excessively high low-temperature temperatures: decomposition of phosphate esters into small molecules, epoxy self-polymerizing oligomers; 2) Excessively high temperatures in the heating phase: intermolecular self-polymerizing polymer gel impurities in acrylic acid double bonds; 3) Insufficient allyl phosphate diethyl ester feed: residual ungrafted EP-POSS raw material; 4) Excessive hydroxyethyl acrylate: free HEA monomers, HEA dimerizing impurities; The severity of the side reactions is indicated based on the peak area ratio of each impurity in the GPC chromatogram. The molecular structure of the five products was analyzed using Fourier transform infrared spectroscopy, ¹H NMR spectroscopy, and ³¹P NMR spectroscopy. In Preparation Example 2, the characteristic absorption peak of epoxy at 910 cm⁻¹ completely disappeared in the infrared spectrum, while the characteristic peaks of Si-O-Si at 1090 cm⁻¹, P=O at 1260 cm⁻¹, carbonyl acrylate at 1726 cm⁻¹, and carbon-carbon double bond at 1632 cm⁻¹ remained intact without any impurity absorption bands. Its ¹H NMR showed only three characteristic proton peaks: δ0.8–1.0 ppm for silane, δ4.0–4.8 ppm for phosphoester methylene, and δ5.8–6.4 ppm for acrylic acid double bond. ³¹P NMR showed only a single sharp main peak at δ7.6 ppm, with no free phosphoester impurity peaks, consistent with Table 1. The quantitative data of the highest yield, lowest total impurity content, and no obvious byproducts in this example are completely consistent; while the infrared spectra of preparation examples 1, 3, 4, and 5 show residual weak epoxy absorption peaks, and the NMR spectra show multiple impurity characteristic peaks, which correspond to the test results in the table of decreased yield, increased total impurity content, and large-scale generation of side reactions. The quantitative GPC data and the spectroscopic qualitative characterization corroborate each other, proving that segmented temperature control and precise raw material molar ratio can suppress side reactions and achieve complete grafting synthesis of APSA monomers.
[0055] A polymerizable monomer, characterized in that it comprises APSA monomer prepared by the above-described method for preparing a phosphorus-silicon bifunctional comonomer and polyethylene glycol diacrylate (PEGDA) monomer. The APSA monomer exhibits high reactivity of the acrylate double bonds, preferentially initiating polymerization during the low-temperature thermal initiation stage, rapidly forming a dense polymer layer at the positive and negative electrode interface. The terminal cage-like siloxane structure of the monomer can physically intercalate and chemically anchor with the hydroxyl groups on the surface of the high-nickel positive electrode and the SEI defect sites of the silicon-carbon negative electrode, achieving a super-strong interfacial bond, precisely sealing oxygen release defects in the high-nickel positive electrode, inhibiting transition metal dissolution, and simultaneously constraining the silicon-carbon negative electrode. Microscopic deformation prevents repeated SEI breakage; the covalently bonded phosphoroyl groups in the middle of the molecule are fixed inside the electrolyte network along with the polymer skeleton, achieving intrinsic flame retardancy of a single molecule, with no precipitation and no failure. It is co-crosslinked with flexible PEGDA auxiliary monomers. The flexible long chains of PEGDA are interspersed in the gaps of the rigid polymer network of APSA to construct a new crosslinking system of "rigid-flexible coupling and in-situ self-gradient". It spontaneously forms an integrated structure with high interfacial anchorage, high bulk flexibility and high overall flame retardancy, which is perfectly adapted to the 200%-300% ultra-large expansion of silicon-carbon anode, while solving the problems of high-temperature corrosion and thermal runaway of high-nickel cathode.
[0056] The mass ratio of APSA monomer to PEGDA monomer in this invention is 20–25:75–80.
[0057] The polymerizable monomers described in this invention also include vinylene carbonate (VC), with the amount of VC added being 1% of the total mass. The trace amount of VC helps to optimize the morphology of the interfacial film and further reduce the interfacial impedance.
[0058] A precursor solution, characterized in that: the precursor solution is composed of the polymerizable monomers described above, a basic electrolyte, an initiator, and an inorganic flame-retardant filler, wherein the proportions of each component are: 60%–70% basic electrolyte, 20%–25% polymerizable monomers, 0.5%–1.0% initiator, and 5%–10% inorganic flame-retardant filler.
[0059] The basic electrolyte of this invention is a composite tri-salt system containing LiPF6, LiBF4, and LiDFOB, with a solvent being a composite solvent of EC, DMC, and FEC. LiDFOB can form a stable CEI film on the positive electrode surface, inhibiting oxygen release and metal dissolution from the high-nickel positive electrode; FEC can optimize the SEI film structure of the silicon-carbon negative electrode, improving the interface flexibility and stability; and LiBF4 enhances the high-temperature stability of the electrolyte and the flame-retardant substrate performance.
[0060] The LiPF6:LiBF4:LiDFOB ratio in this invention is 1.0:0.2:0.1, and the volume ratio of EC, DMC, and FEC is 3:5:2.
[0061] The initiator described in this invention is AIBN (azobisisobutyronitrile), which can achieve low-temperature thermal initiation polymerization at 50–60℃, avoiding damage to the high-nickel cathode and silicon-carbon anode structures during high-temperature treatment.
[0062] The inorganic flame-retardant filler of this invention is a compound of nano-Al2O3 and EP-POSS cage-type silsesquioxane in a mass ratio of 3:1. Nano-Al2O3 improves the heat resistance, insulation and impact resistance of the system, while the EP-POSS cage-like porous structure can effectively lock the electrolyte and prevent the leakage of free liquid, while improving the cross-linking network strength and flame-retardant and smoke-suppressing ability.
[0063] A lithium-ion battery includes a positive electrode, a negative electrode, and a separator, characterized in that it further includes the precursor solution described above.
[0064] The positive electrode of this invention is a high-nickel ternary material, either NCM811 or NCM955, and adopts... Al³⁺、Zr 4 ⁺ The electrode is doped with two elements, with a total molar fraction of 0.5%–1.0%, and uniformly coated with a 5–10 nm LiPO3 inorganic ceramic protective layer. The two elements doping can stabilize the layered lattice of the cathode and suppress oxygen release and lattice collapse at high temperatures. The LiPO3 coating layer can block the contact between the electrolyte and the active interface of the cathode, greatly reduce the dissolution of transition metals and interfacial side reactions, and improve the thermal stability and voltage resistance of the cathode.
[0065] The negative electrode of this invention is a nano-silicon-carbon nanotube-graphite composite silicon-carbon material with a silicon content of 15%–20%. The surface of the negative electrode is uniformly coated with a 1–2 μm rigid conductive composite coating, which is composed of carbon nanotubes and polyimide resin. The three-dimensional carbon network structure can buffer the large volume expansion of silicon, and the rigid coating can constrain the overall deformation of the negative electrode, avoid repeated damage and regeneration of the SEI film, and uniform current distribution on the electrode surface, thereby suppressing lithium dendrite growth and negative electrode gas generation problems from the root.
[0066] The separator described in this invention is a polypropylene-based ceramic-coated separator with a 2–3 μm alumina ceramic coating on its surface. The separator has a heat shrinkage temperature ≥180℃, which can effectively resist high-temperature shrinkage, resist lithium dendrite puncture, and improve the internal short-circuit protection capability of the battery cell.
[0067] A method for preparing a lithium-ion battery, characterized by comprising the following steps: S1. Prepare the precursor solution, stir evenly, and then degas under vacuum. S2. Assemble the positive and negative electrodes and the separator to form the battery cell; S3. Inject the precursor solution obtained in step S1 into the cell formed in step S2 under vacuum conditions; let it stand at room temperature for 2 hours to soak, and then perform thermal initiation polymerization at 55°C for 3–5 hours to form a gel electrolyte in situ; the curing temperature is ≤60°C throughout the process, without high temperature damage to the electrode structure, and there is no free liquid electrolyte inside the cell. After cooling, sealing, formation, and capacity testing, the finished battery is obtained.
[0068] The battery described in this invention has an energy density of ≥380Wh / kg and has passed the 150℃ high-temperature hot box, needle penetration, heavy object impact, and 8V overcharge safety tests. It does not catch fire, explode, or leak liquid throughout the entire process.
[0069] Examples and comparative examples of lithium-ion battery manufacturing methods are given below: Example 1: S1. Preparation of precursor solution: Based on a total mass of 100 g of precursor solution, weigh 70.00 g of basic electrolyte, 22.00 g of polymerizable monomer, 0.80 g of AIBN azobisisobutyronitrile initiator, and 7.20 g of composite flame retardant filler in sequence. The basic electrolyte components are: lithium salt system consisting of 1.0 mol / L LiPF6, 0.2 mol / L LiBF4, and 0.1 mol / L LiDFOB; solvent consisting of ethylene carbonate EC, dimethyl carbonate DMC, and fluoroethylene carbonate FEC in a volume ratio of 3:5:2. The total mass of polymerizable monomers is 22.00 g, including 22 parts by mass of APSA monomer and 78 parts by mass of PEGDA, i.e., 4.84 g of APSA and 17.16 g of PEGDA, plus an additional 1% of the total mass of polymerizable monomers of VC, i.e., 0.22 g of vinylene carbonate. The total mass of the composite flame-retardant filler is 7.20 g, and the mass ratio of nano-alumina Al2O3 to EP-POSS cage-type silsesquioxane is 3:1. Weigh 5.40 g of nano-Al2O3 and 1.80 g of EP-POSS. The above materials were sequentially added to the mixing vessel, and the system was sealed to isolate moisture. The mixture was stirred at 3000 rpm for 60 minutes to ensure that the flame-retardant filler was evenly dispersed and that each monomer was fully miscible with the electrolyte. After stirring, the mixture was transferred to a vacuum degassing device and vacuum degassed at room temperature for 30 minutes to completely eliminate micro bubbles in the system and finally obtain a low-viscosity, highly wettable in-situ polymerized electrolyte precursor. S2. Cell fabrication: The positive electrode uses Al and Zr double-doped NCM811 with a total doping amount of 0.8 mol%, and is coated with an 8 nm LiPO3 coating. The positive electrode active material accounts for 96% and the areal density is 18 mg / cm². The negative electrode uses a silicon-carbon composite material with a silicon content of 18%, and is coated with a rigid conductive coating composed of 1.5 μm carbon nanotubes and polyimide. The separator is a PP separator coated with 2.5 μm alumina. The positive electrode, silicon-carbon negative electrode, and separator are wound / stacked, and sealed with an aluminum-plastic film on three sides, with a liquid injection port reserved to obtain a dry soft-pack battery cell. S3. Low-temperature vacuum liquid injection: Under vacuum conditions, inject the in-situ polymerized electrolyte precursor obtained in step S1 into the cell formed in step S2; the electrolyte is injected and soaked for 2 hours, and the precursor is allowed to fully wet the electrode pores and diaphragm pores by vacuum standing, so as to ensure that the monomer and conductive agent uniformly cover the electrode interface. S4: In-situ low-temperature polymerization of soft-pack cells: The soft-pack cells obtained in S3 with completed electrolyte injection are placed in a 55°C high-temperature environment for constant temperature curing for 4 hours. During this process, the acrylic double bonds at the end of the APSA monomers and the PEGDA double bonds undergo cross-linking polymerization, generating a three-dimensional cross-linked organic-inorganic composite polymer network in situ inside the cell. At the same time, the network conductive pathway is covalently fixed, realizing the overall curing of the electrolyte from a liquid state to a semi-solid gel structure. S5: Sealing and Formation: After isothermal polymerization, the battery cell is naturally cooled to room temperature (25°C). The pre-reserved injection port of the soft-pack battery cell is then heat-sealed at a temperature of 160°C, a pressure of 0.3 MPa, and a sealing edge width of 5 mm. After sealing, the battery cell is pressure-shaped using a flatbed shaping machine at a pressure of 0.25 MPa for 15 minutes to eliminate warping of the internal electrode sheets and interlayer gaps, ensuring tight adhesion of the electrode sheets, separator, and gel electrolyte. After shaping, the battery cell is transferred to the formation equipment for a low-current pre-formation process. The pre-formation charging current is set at 0.02 C, and constant current charging is performed to 4.2 V before switching to constant voltage charging with a cutoff current of 0.005 C. The total pre-formation time for a single process is 120 minutes. Through slow film formation at low current, a uniform and stable CEI / SEI interface film is constructed on the positive and negative electrode surfaces. After pre-formation, the battery cell is placed in a 25°C room temperature environment for static aging for 48 hours. h, releases trace amounts of by-product gas inside the cell, simultaneously stabilizing the cross-linked network of the gel electrolyte and the electrode interface structure, completing the entire preparation process, and obtaining an in-situ polymerized semi-solid soft-pack battery with stable interface, no bulging, and no free electrolyte.
[0070] Example 2 S1. Preparation of Precursor Solution: Based on a total mass of 100 g of precursor solution, weigh out 60.00 g of basic electrolyte, 25.00 g of polymerizable monomer, 1.00 g of AIBN azobisisobutyronitrile initiator, and 10.00 g of composite flame-retardant filler. The basic electrolyte is a 1.0 mol / L LiPF6 + 0.2 mol / L LiBF4 + 0.1 mol / L LiDFOB composite lithium salt system, with solvents EC, DMC, and FEC mixed in a volume ratio of 3:5:2. The total weight of polymerizable monomer is 25.00 g, including 5.50 g of APSA monomer and 19.50 g of PEGDA monomer. An additional 1% (0.25 g) of VC (ethylene carbonate) is added to the total mass of the polymerizable monomer. The total weight of the composite flame-retardant filler is 10.00 g, including 7.50 g of nano-Al2O3 and 2.50 g of EP-POSS. g, the mass ratio of the two is 3:1; all materials are put into the mixing vessel, the mixing vessel is placed in an anhydrous and oxygen-free glove box, and the mixture is stirred at 3000 rpm for 60 min. After stirring, the mixture is degassed under vacuum at room temperature for 30 min to remove the micro bubbles in the system and obtain a low viscosity, high wettability polymerizable electrolyte precursor. S2-S5 are the same as in Example 1.
[0071] Example 3 S1. Preparation of Precursor Solution: Based on a total mass of 100 g of precursor solution, weigh out 70.00 g of basic electrolyte, 20.00 g of polymerizable monomer, 0.50 g of AIBN azobisisobutyronitrile initiator, and 5.00 g of composite flame-retardant filler. The basic electrolyte is a 1.0 mol / L LiPF6 + 0.2 mol / L LiBF4 + 0.1 mol / L LiDFOB composite lithium salt system, with solvents EC, DMC, and FEC mixed in a volume ratio of 3:5:2. The total mass of polymerizable monomer is 20.00 g, including 4.40 g of APSA monomer and 15.60 g of PEGDA monomer. An additional 1% (1% by mass) of VC (0.20 g) of vinylene carbonate is added. The total mass of the composite flame-retardant filler is 5.00 g, including 3.75 g of nano-Al2O3 and 1.25 g of EP-POSS. g, the mass ratio of the two is 3:1; all materials are mixed in an anhydrous and oxygen-free glove box and stirred at 3000 rpm for 60 min. After stirring, vacuum degassing is performed at room temperature for 30 min to remove micro bubbles in the system, and a low-viscosity, highly wettable polymerizable electrolyte precursor is obtained. S2-S5 are the same as in Example 1.
[0072] Comparative Example 1 (Traditional Liquid Electrolyte System) The conventional 1.0M LiPF6 EC / DMC=3:7 liquid electrolyte was used, and the assembly process of the electrodes, separator, and cell was completely consistent with that of Example 1, without any in-situ curing process.
[0073] S1. Preparation of electrolyte: A conventional 1.0 mol / L LiPF6 liquid electrolyte is used. The electrolyte solvent is a mixture of EC and DMC in a volume ratio of 3:7. In an argon glove box with water and oxygen <1 ppm, 252.41 g of melted and dehydrated EC and 602.46 g of dry DMC are mixed to obtain a 3:7 mixed solvent. 145.14 g of dry LiPF6 is added in batches at low temperature and stirred continuously until completely dissolved. After standing to remove bubbles and testing for moisture and acidity, 1 kg of the above electrolyte is obtained. S2. Cell fabrication: The positive electrode uses Al and Zr double-doped NCM811 with a total doping amount of 0.8 mol%, and is coated with an 8 nm LiPO3 coating. The positive electrode active material accounts for 96% and the areal density is 18 mg / cm². The negative electrode uses a silicon-carbon composite material with a silicon content of 18%, and is coated with a rigid conductive coating composed of 1.5 μm carbon nanotubes and polyimide. The separator is a PP separator coated with 2.5 μm alumina. The positive electrode, silicon-carbon negative electrode, and separator are wound / stacked, and sealed with an aluminum-plastic film on three sides, with a liquid injection port reserved to obtain a dry soft-pack battery cell. S3, Low-temperature vacuum liquid injection: The electrolyte obtained in step S1 is injected into the cell formed in step S2 under vacuum conditions; the electrolyte is injected and soaked for 2 hours, and the precursor is allowed to fully wet the electrode pores and diaphragm pores by vacuum standing, so as to ensure that the monomer and conductive agent uniformly cover the electrode interface. S4: Sealing and Formation: The pre-reserved injection port of the soft-pack battery cell is heat-sealed at a temperature of 160℃, a pressure of 0.3 MPa, and a sealing edge width of 5 mm. After sealing, the cell is pressure-shaped using a flatbed shaping machine at a pressure of 0.25 MPa for 15 minutes to eliminate warping of the internal electrode sheets and interlayer gaps, ensuring tight adhesion of the electrode sheets, separator, and gel electrolyte. After shaping, the cell is transferred to the formation equipment for a low-current pre-formation process. The pre-formation charging current is set at 0.02C, and constant current charging is performed to 4.2V before switching to constant voltage charging with a cutoff current of 0.005C. The total pre-formation time for a single process is 120 minutes. Through slow film formation at low current, a uniform and stable CEI / SEI interface film is constructed on the positive and negative electrode surfaces. After pre-formation, the cell is placed in a 25℃ ambient temperature environment for static aging for 48 hours. h, releases trace amounts of by-product gas inside the cell, simultaneously stabilizing the cross-linked network of the gel electrolyte and the electrode interface structure, completing the entire preparation process, and obtaining a traditional liquid soft-pack battery.
[0074] Comparative Example 2: A conventional commercial PEGDA single-monomer curing system was used. S1. Preparation of Precursor Solution: Based on a total mass of 100 g of precursor solution, weigh out 70.00 g of basic electrolyte, 22.00 g of polymerizable monomer, 0.80 g of AIBN azobisisobutyronitrile initiator, and 7.20 g of composite flame-retardant filler. The basic electrolyte is a 1.0 mol / L LiPF6 + 0.2 mol / L LiBF4 + 0.1 mol / L LiDFOB composite lithium salt system, with solvents EC, DMC, and FEC mixed in a volume ratio of 3:5:2. The total weight of the polymerizable monomer is 22.00 g, all of which are PEGDA monomers, without the addition of APSA phosphorus-silicon bifunctional comonomer, and an additional 1% (0.22 g) of VC (ethylene carbonate) is added to the total mass of the polymerizable monomer. The total weight of the composite flame-retardant filler is 7.20 g, consisting of 5.40 g of nano-Al2O3 and 1.80 g of EP-POSS. g, the mass ratio of the two is 3:1; all materials are put into the mixing vessel, the mixing vessel is placed in an anhydrous and oxygen-free glove box, and the mixture is stirred at 3000 rpm for 60 min. After stirring, the mixture is degassed under vacuum at room temperature for 30 min to remove the tiny bubbles in the system and obtain the polymerizable electrolyte precursor. S2-S5 are the same as in Example 1.
[0075] Comparative Example 3 (Compared to Example 1, only the ratio of APSA to PEGDA within the polymerizable monomer S1 was adjusted) S1. Preparation of Precursor Solution: Based on a total mass of 100 g of precursor solution, weigh out 70.00 g of basic electrolyte, 22.00 g of polymerizable monomer, 0.80 g of AIBN azobisisobutyronitrile initiator, and 7.20 g of composite flame-retardant filler. The basic electrolyte is a 1.0 mol / L LiPF6 + 0.2 mol / L LiBF4 + 0.1 mol / L LiDFOB composite lithium salt system, with solvents EC, DMC, and FEC mixed in a volume ratio of 3:5:2. The total mass of polymerizable monomer is 22.00 g, including 1.10 g of APSA monomer and 20.90 g of PEGDA monomer in a mass ratio of 5:95. Add an additional 1% (1% by mass) of VC (0.22 g) of vinylene carbonate. The total mass of the composite flame-retardant filler is 7.20 g, including 5.40 g of nano-Al2O3 and 1.80 g of EP-POSS. g, the mass ratio of the two is 3:1; All materials were put into a mixing tank, which was placed in an anhydrous and oxygen-free glove box. The mixture was stirred at 3000 rpm for 60 minutes. After stirring, the mixture was degassed under vacuum at room temperature for 30 minutes to remove tiny bubbles from the system, resulting in a low-viscosity, highly wettable polymerizable electrolyte precursor. S2-S5 are the same as in Example 1.
[0076] The following performance tests were performed on the pouch cells prepared in Examples 1-3 and Comparative Examples 1-3: 1. The pouch cells prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to a 150°C hot box test. For each test, one pouch cell from Examples 1-3 and Comparative Examples 1-3 was used for testing. Taking a single battery test as an example, the test method is as follows: 1) Let the fully charged 4.6V soft-pack battery stand at room temperature for 2 hours, and record the initial thickness, voltage and temperature of the soft-pack battery; 2) Place the pouch battery into a programmable constant temperature chamber. The initial temperature of the chamber is room temperature. The temperature is increased to 150°C at a constant rate of 5°C / min and held at that temperature for 30 min. 3) Monitor the voltage, surface temperature, and thickness changes of the pouch battery in real time throughout the process, and observe whether there are any phenomena such as bulging, leakage, smoke, fire, or explosion; 4) Judgment criteria: No fire or explosion is considered qualified.
[0077] 2. The soft-pack batteries prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to a needle penetration test (3mm steel needle): Taking a single pouch battery test as an example, the test method is as follows: 1) The soft-pack battery is fully charged to 4.6V and left to stand at room temperature for 2 hours; 2) Fix the soft-pack battery on the test bench, and use a solid steel needle with a diameter of 3mm to penetrate the middle of the soft-pack battery at a constant speed perpendicular to the plane of the electrode. The steel needle remains in the penetrated state for 1 hour. 3) Record the temperature and voltage changes of the pouch battery throughout the entire process, and observe for any smoke, fire, or explosion; 4) Judgment criteria: No open flame or explosion after needle puncture is considered qualified.
[0078] 3. The pouch cells prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to an 8V overcharge test. Taking a single pouch battery test as an example, the test method is as follows: 1) The soft-pack battery is left at room temperature with an initial voltage of 4.6V (fully charged state). 2) Use constant current 0.5C for continuous charging, set the charging cutoff voltage to 8V, and set the upper limit of charging time to 2 hours; 3) Real-time acquisition of surface temperature, voltage, and thickness of pouch batteries to observe bulging, leakage, and fire conditions; 4) Judgment criteria: It is considered qualified if no fire or explosion occurs during the overcharging process.
[0079] 4. The soft-pack batteries prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to a heavy object impact test (10 kg / m): Taking a single pouch battery test as an example, the test method is as follows: 1) Fully charge the soft-pack battery to 4.6V and let it stand at room temperature for 2 hours; 2) Place the pouch battery flat on a rigid steel plate platform, aligning the center of the battery with the impact point; 3) A standard 10kg weight is dropped vertically from a height of 1m to impact the center of the pouch battery in a single impact. 4) After the impact, observe the plant for 1 hour, record the temperature and appearance changes, and check for smoke or fire. 5) Judgment criteria: It is considered qualified if there is no fire or explosion after impact.
[0080] 5. The capacity retention rates of the pouch cells prepared in Examples 1-3 and Comparative Examples 1-3 were determined after 500 cycles at 60°C. Taking a single pouch battery test as an example, the test method is as follows: 1) Set the constant temperature chamber to 60℃, and place the soft-pack battery inside the chamber to keep it warm for 1 hour; 2) Charge and discharge cycle: Charge to 4.6V at 0.2C constant current and constant voltage, cut-off current 0.02C; let stand for 10 min; discharge to 2.7V at 0.2C constant current, let stand for 10 min, and this is recorded as one complete cycle; 3) Perform 500 consecutive cycles, recording the discharge capacity every 100 cycles; 4) Formula for calculating capacity retention rate: 500 discharge capacity ÷ first discharge capacity × 100%.
[0081] 6. The cell energy density (Wh / kg) of the pouch cells prepared in Examples 1-3 and Comparative Examples 1-3 was measured respectively: Taking a single pouch battery test as an example, the test method is as follows: 1) At room temperature (25℃), charge to 4.6V using a constant current and constant voltage at 0.2C, and discharge to 2.7V using a constant current at 0.2C. Record the discharge capacity (in Ah) and average discharge voltage (V). 2) Weigh the total mass of the intact soft-pack battery using a high-precision electronic balance (excluding excess scraps of the outer packaging aluminum-plastic film, unit: kg). 3) Volumetric energy density can be measured: the overall volume of the pouch cell is measured using the water displacement method; 4) Formula for calculating mass energy density: (discharge capacity × average discharge voltage) ÷ total mass of pouch battery, unit Wh / kg.
[0082] 7. The soft-pack batteries prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to 2000 cycles of impedance amplification: Taking a single pouch battery test as an example, the test method is as follows: 1) At 25℃ ambient temperature, standard charge / discharge cycle: 0.5C charge to 4.6V, 0.5C discharge to 2.7V; 2) After the discharge ends at the 0th cycle (initial state) and the 2000th cycle, and after standing for 30 minutes, the AC internal resistance of the cell at 1000Hz is tested using an AC impedance tester. 3) Impedance increase calculation formula: (2000 turns internal resistance − initial internal resistance) ÷ initial internal resistance × 100%.
[0083] Table 2. Results of the soft-pack batteries prepared in Examples 1-3 and Comparative Examples 1-3 under the following conditions: 150℃ hot box test, needle penetration test (3mm steel needle), 8V overcharge test, 500-cycle capacity retention at 60℃, cell energy density (Wh / kg), and impedance amplification test at 2000 cycles. Table 2 presents the test results of the soft-pack batteries prepared in Examples 1-3 and Comparative Examples 1-3 under the following conditions: 150℃ hot box test, needle penetration test (3mm steel needle), 8V overcharge test, 500 cycles at 60℃ high temperature, capacity retention rate, cell energy density (Wh / kg), cell energy density (Wh / kg), and impedance increase after 2000 cycles. From the test data, it can be seen that the in-situ curing scheme of the present invention can completely solve the safety defects of the traditional system while basically retaining the ultra-high energy density of the high-nickel silicon-carbon system. Compared with the conventional curing system, the flame retardancy, resistance to thermal runaway, and interface stability are greatly improved, and the overall performance is optimal.
[0084] A comparative analysis was conducted on all seven test data points from Examples 1, 2, and 3 (the system of this invention), Comparative Example 1 (traditional liquid electrolyte), and Comparative Example 2 (PEGDA curing only, without APSA phosphosilicate monomer). First, this invention can fully retain the high energy density advantage of the high-nickel-silicon-carbon system without sacrificing cell capacity due to the semi-solid curing process. The energy density of Example 1 is 382 Wh / kg, Example 2 is 378 Wh / kg, and Example 3 is 385 Wh / kg; Comparative Example 1 uses a traditional liquid electrolyte with 388 Wh / kg, and Comparative Example 2 uses a common PEGDA curing system with 381 Wh / kg. It can be seen that the energy density range of the three examples of this invention is stable between 378 and 385 Wh / kg, with very little difference from the values of Comparative Example 1 and Comparative Example 2, and there is no significant attenuation. This indicates that the entire system of APSA monomer, in-situ cross-linking gel curing, and compound inorganic flame-retardant filler introduced by this invention will not block electrode pores or seriously reduce lithium-ion migration efficiency. It can fully retain the high specific capacity advantage of the high-nickel ternary cathode and silicon-carbon anode, achieving a balance between high energy density and high safety performance, and solving the pain point of the significant drop in energy density caused by the densification of the cross-linking network in existing gel batteries. Secondly, the in-situ cross-linked gel system completely locks in the electrolyte, and after four rigorous safety tests, it shows no thermal runaway, no fire, and no explosion, making its safety performance far superior to traditional liquid and ordinary single-solidification systems. (1) Supporting data from the 150℃ hot box test: Example 1: No abnormalities after 30 min of heat preservation; Example 2: No abnormalities after 28 min of heat preservation; Example 3: No abnormalities after 25 min of heat preservation; Comparative Example 1: Thermal runaway explosion occurred after only 12 min; Comparative Example 2: Budding and fire occurred after 18 min of heat preservation. It can be seen that under high temperature, traditional liquid electrolytes lack network binding, the solvent decomposes rapidly to produce gas, and a large amount of flammable components are released, triggering thermal runaway in a short time; the ordinary curing system of PEGDA lacks phosphorus flame retardant groups and cage-type siloxane heat-suppressing structure, and the cross-linked network is easily damaged and leaked under high temperature, resulting in bulging and combustion; while the APSA monomer of this invention has covalent phosphorus and oxygen flame retardant segments, and together with Al2O3 / EP-POSS composite inorganic filler to construct a three-dimensional liquid-locking network, it inhibits electrolyte decomposition, blocks oxygen, and captures free radicals under high temperature. The battery cell has no leakage or open flame under long-term high temperature environment, and the heat resistance limit is significantly improved; (2) Supporting data from the 3mm steel needle penetration test: Examples 1-3: No fire, explosion, or leakage after needle puncture; Comparative Example 1: Instant ignition and combustion upon needle puncture; Comparative Example 2: Localized smoke and fire upon needle puncture. It can be seen that needle puncture causes a short circuit and heat generation within the battery cell, leading to a large leakage of liquid electrolyte which is directly ignited upon contact with high temperature. Ordinary PEGDA gel lacks an intrinsic flame-retardant molecular structure; after the network ruptures at the puncture site, liquid electrolyte flows out, resulting in smoke and fire. The cross-linked network of this invention firmly binds the electrolyte, while the phosphorus groups of APSA molecules rapidly form a flame-retardant char layer at the high temperature of the puncture site, isolating heat from flammable media and preventing open flame generation. (3) 8V overcharge test data support: Example 1: No bulging, no fire, voltage drop is normal; Examples 2 and 3: Only slight temperature rise, no abnormalities; Comparative Example 1: Bulging, fire, and explosion after 12 minutes of charging; Comparative Example 2: Local thermal runaway occurs after 20 minutes of charging. It can be seen that under overcharge conditions, the high-nickel cathode releases a large amount of oxygen, catalyzing the electrolyte to undergo violent oxidation and exothermic reactions; traditional liquid electrolytes and ordinary gel systems lack long-term flame-retardant structures, and the continuous accumulation of heat leads to explosions; The cage-like siloxane structure of this invention can adsorb the active oxygen released by the cathode, and the phospho groups inhibit the exothermic oxidation reaction. Even if the voltage is severely exceeded, the cell temperature only rises slightly, with no risk of bulging or thermal runaway. (4) Supporting data from heavy object impact tests: Examples 1-3: No damage, leakage, or fire occurred in the casing after impact; Comparative Example 1: Casing ruptured, leaked, and caught fire; Comparative Example 2: Casing deformed and continuously emitted smoke. It can be seen that the external impact caused internal tearing of the electrode, resulting in a large leakage of liquid electrolyte. The mechanical strength of ordinary single PEGDA crosslinking network is insufficient, and the network breaks after impact, leading to electrolyte leakage. The APSA rigid cage structure of this invention forms a rigid-flexible coupled crosslinking skeleton with PEGDA flexible segments, and is combined with nano-alumina filler to improve impact resistance. After impact, the gel structure remains intact, with no leakage of free electrolyte, eliminating the conditions for combustion from the source. Third, the crosslinking system containing APSA phosphorus silicon monomers significantly improves high-temperature cycling stability and effectively suppresses interfacial side reactions and capacity decay at high temperatures. The capacity retention rate after 500 cycles at 60°C is 92.0% in Example 1, 90.5% in Example 2, and 89.8% in Example 3; compared to only 65.0% in Comparative Example 1 and only 78.2% in Comparative Example 2. It can be seen that high-temperature environments accelerate the dissolution of transition metals in high-nickel cathodes and repeated damage to the SEI of silicon-carbon anodes. Traditional liquid electrolytes lack interfacial modification structures, and side reactions continuously consume active lithium, resulting in a precipitous drop in capacity. The PEGDA curing system alone lacks a siloxane anchoring structure and cannot stabilize the electrode interface, resulting in severe capacity decay. The APSA monomer cage-like siloxane end groups of this invention can be anchored on the surfaces of the positive and negative electrodes, sealing oxygen release defects in the positive electrode and buffering the volume expansion of silicon-carbon. The mid-section phosphorus group inhibits high-temperature oxidation of the electrolyte, significantly reducing irreversible side reactions. The capacity retention rate after 500 high-temperature cycles is much higher than that of the two comparative examples, and the high-temperature service life is significantly extended. Fourth, APSA constructs a stable electrode interface, significantly reducing the impedance increase during long-cycle processes, and ensuring long-term controllable cell polarization. After 2000 cycles, the impedance increase is ≤15% in Example 1, ≤18% in Example 2, and ≤20% in Example 3; compared to ≥60% in Comparative Example 1 and ≥35% in Comparative Example 2, it can be seen that under long-cycle charge and discharge, the silicon-carbon anode continuously expands and contracts, and the high-nickel cathode continuously dissolves metal ions. The SEI in the traditional liquid system repeatedly thickens, and the interface impedance continues to soar. Ordinary PEGDA gel has no interface modification function and cannot inhibit metal ion shuttle and malignant SEI growth. In this invention, the APSA monomer is permanently fixed at the electrode interface after polymerization, constructing a stable protective layer, reducing the repeated generation of SEI, and the three-dimensional cross-linked network ensures the long-term continuity of ion channels. The internal resistance increase is controlled within 20% after 2000 long cycles, resulting in small long-term charge and discharge polarization and stable power performance of the cell.
[0085] Due to the above-mentioned structure, this invention has the advantages of diversified single-cell functions, prevention of leakage and combustion, suppression of thermal runaway, stabilization of positive and negative electrode interfaces, elimination of lithium dendrite growth conditions, and significant improvement of the overall safety of high-nickel silicon-carbon system batteries.
Claims
1. A phosphorus-silicon bifunctional comonomer, characterized in that... Its chemical structural formula is as follows: 。 2. The phosphorus-silicon bifunctional comonomer according to claim 1, characterized in that: The molecular structure of the phosphorus-silicon bifunctional copolymer is characterized by an acrylic acid double bond polymer group at one end, a phosphorus-oxygen flame retardant molecular chain grafted in the middle, and a cage-like siloxane rigid anchoring structure at the end.
3. A method for preparing a phosphorus-silicon bifunctional comonomer, characterized in that: Includes the following steps: Step 1: Raw material pretreatment: Cage-type epoxy silsesquioxane (EP-POSS), diethyl allyl phosphate, and hydroxyethyl acrylate are used as reaction raw materials, anhydrous tetrahydrofuran (THF) is used as the reaction solvent, and triethylamine is used as the acid-binding agent and catalyst. The above raw materials are subjected to dehydration treatment. The second step is a low-temperature nucleophilic addition reaction: Under nitrogen protection and an anhydrous and oxygen-free environment, cage-type epoxy silsesquioxane EP-POSS and diethyl allyl phosphate are added to anhydrous THF solvent, dissolved by stirring in an ice-water bath at 0–10°C, and triethylamine is slowly added dropwise. After the addition is completed, the reaction is kept at a constant temperature for 2 hours to obtain the phosphorus-functionalized POSS intermediate. The third step is end-group double bond grafting modification: the reaction system is heated to 28–35℃, hydroxyethyl acrylate is slowly added dropwise, and the reaction is continuously stirred for 4–6 hours to obtain the target crude product with double bond polymerization activity, phosphorus flame retardancy and siloxane anchoring. The fourth step is purification and drying: After the reaction is completed, the triethylamine salt byproduct is removed by washing with deionized water and the organic phase is collected; the THF solvent is removed by rotary evaporation, and then the liquid is dried under vacuum to remove water and impurities, finally obtaining a light yellow transparent viscous liquid, named allyl phosphoryl cage siloxane acrylate, abbreviated as APSA monomer.
4. The method for preparing a phosphorus-silicon bifunctional comonomer according to claim 3, characterized in that: The molar ratio of the cage-like epoxy silsesquioxane (EP-POSS), allyl phosphate diethyl ester, and hydroxyethyl acrylate is 1:(0.9-1.1):(1.05-1.3); the content of the anhydrous tetrahydrofuran (THF) is 5-7 times the total mass of the cage-like epoxy silsesquioxane (EP-POSS), allyl phosphate diethyl ester, and hydroxyethyl acrylate; the amount of triethylamine added is 3%-5% of the total molar mass of the reaction system; in the fourth step, the vacuum drying temperature is 45℃ and the drying time is 12h; the molecular weight of the APSA monomer is 1180-1220 g / mol.
5. A polymerizable monomer, characterized in that: The polymerizable monomer includes APSA monomer prepared by the method for preparing a phosphorus-silicon bifunctional comonomer as described in claim 3 or 4 above, and polyethylene glycol diacrylate (PEGDA) monomer, wherein the mass ratio of APSA monomer to PEGDA monomer is 20–25:75–80, and the polymerizable monomer also includes vinylene carbonate (VC).
6. A precursor solution, characterized in that: The precursor solution comprises the polymerizable monomer described in claim 5, as well as a basic electrolyte, an initiator, and an inorganic flame-retardant filler, wherein the proportions of each component are: 60%–70% basic electrolyte, 20%–25% polymerizable monomer, 0.5%–1.0% initiator, and 5%–10% inorganic flame-retardant filler.
7. A precursor solution according to claim 6, characterized in that: The basic electrolyte is a composite tri-salt system containing LiPF6, LiBF4, and LiDFOB. The solvent is a compound solvent of EC, DMC, and FEC, with the LiPF6:LiBF4:LiDFOB ratio being 1.0:0.2:0.1 and the volume ratio of EC, DMC, and FEC being 3:5:
2. The initiator is AIBN (azobisisobutyronitrile), and the inorganic flame-retardant filler is a compound of nano-Al2O3 and EP-POSS cage-type silsesquioxane in a mass ratio of 3:
1.
8. A lithium-ion battery, comprising a positive electrode, a negative electrode, and a separator, characterized in that: It also includes the precursor solution described in claim 6 or 7 above.
9. A lithium-ion battery according to claim 8, characterized in that: The positive electrode is a high-nickel ternary material, either NCM811 or NCM955, using Al³⁺ and Zr. 4 The anode material is a bi-element lattice doped material with a total doping molar fraction of 0.5%–1.0%, and is uniformly coated with a 5–10 nm LiPO3 inorganic ceramic protective layer. The cathode is a nano-silicon-carbon nanotube-graphite composite silicon-carbon material with a silicon content of 15%–20%. The anode surface is uniformly coated with a 1–2 μm rigid conductive composite coating, which is composed of carbon nanotubes and polyimide resin. The separator is a polypropylene-based ceramic-coated separator with a 2–3 μm alumina ceramic coating on the surface, and the separator has a heat shrinkage temperature ≥180℃.
10. A method for preparing a lithium-ion battery as described in claim 8, characterized in that: Includes the following steps: S1. Prepare the precursor solution, stir evenly, and then degas under vacuum. S2. Assemble the positive and negative electrodes and the separator to form the battery cell; S3. Under vacuum conditions, inject the precursor solution obtained in step S1 into the cell formed in step S2; let it stand at room temperature for 2 hours to soak, then perform thermal initiation polymerization at 55°C for 3–5 hours to form a gel electrolyte in situ. Cool, seal, form, and measure the capacity to obtain the finished battery.